Electrochemically synthesized potassium ferrate for diclofenac degradation: Performance, kinetics, and mechanistic insights - Chia-Hung Chen; Ching-Lung Chen; Hsin-Yu Chiang; Wu-Xing Chen; Amila Kasun Abeysinghe; Fang-Yu Liang; Chih-Chi Yang; Yen-Ping Peng (Journal of Water Process Engineering, 2026)

Interface-decoupled oxygen reduction via atomic Pt–Pd–Co clusters and vacancy-mediated kinetic buffering in a hierarchical carbon-supported multimetallic oxide platform - Yang-Yang Hsu; Ching-Hua Fan; Yu-Lin LEE; Sheng Dai; Kuan-Wen Wang; Nozomu Hiraoka; Hirofumi Ishii; Ting-Shan Chan; Chia-Shing Wu; Guo-Wei Lee; Po-Chun Chen; Tsan-Yao Chen (Chemical Engineering Journal, 2026)

Regulating cation disorder to stabilize oxygen redox in Li-rich DRX cathodes via Fe substitution - Chia-Ching Lin; Péter Udvarhelyi; Hao-Hsiang Chang; Tsung-Yi Chen; Zhenfei Cai; Yu Zhao; Han-Yi Chen; Denis Y.W. Yu (Chemical Engineering Journal, 2026)

Chlorpyrifos exposure induces inflammatory and immune dysregulation: An integrative in silico and in vitro analysis - Chen-Yu Chiang; Shih-Pin Chen; Ci-Wen Luo; Chun-Hung Su; Shiuan-Shinn Lee; Wen-Ying Chen; Chun-Jung Chen; Ching-Chi Tseng; Pin-Tzu Chen; Yin-Che Lu; Yu-Hsiang Kuan (Pesticide Biochemistry and Physiology, 2026)

Probabilistic seismic hazard assessment for Taiwan: Updates and improvements in TEM PSHA2025 - Jia-Cian Gao; Jo-Chen Kao; Chung-Han Chan; Ray Y. Chuang; Cheng-Hung Chen; J. Bruce H. Shyu; Kuo-En Ching; Yu Wang; Kuo-Fong Ma (Engineering Geology, 2026)

Piezo-coupled triboelectric self-powered tactile sensor based on a self-healable polymer for object recognition - Manikandan Venkatesan; Wei-Wen Chen; Yu-Chen Wang; Yung-Chi Hsu; Jayashree Chandrasekar; Hao-Yuan Chen; Shih-Yu Lin; Chia-Jung Cho; Shang-Jui Huang; Ming-An Chung; Wen-Ya Lee; Yu Wen; et al. (Chemical Engineering Journal, 2026)

Correction: Volatile Compounds from Endophytic PGPM Improve Copper Tolerance by Regulating Redox Balance in Cauliflower - Jing-Yu Chen; Tri-Phuong Nguyen; Chih-Cheng Lin; Ching-Han Chang; Hieng-Ming Ting; Ping-Fu Hou; Hao-Jen Huang (Journal of Plant Growth Regulation, 2026)

Aurone analog LYK01 exerts oxidative stress-dependent antiproliferation, G2/M arrest, apoptosis, and DNA damage of oral cancer cells involving MAPK modulation - Yan-Ning Chen; Chia-Hung Yen; Ching-Yu Yen; Ammad Ahmad Farooqi; Meng-Yang Chang; Tsu-Ming Chien; Jen-Yang Tang; Hsueh-Wei Chang (Molecular and Cellular Biochemistry, 2026)

Longitudinal association between dietary quality trajectories and cognitive frailty in older adults: a 12-year study of the TIGER cohort - Ting-I. Lee; Bo-Yu Hsiao; Te-Hsuan Huang; Ling-Wei Chen; Yi-Chun Chou; Meei-Shyuan Lee; Jeng-Min Chiou; Yen-Ching Chen; Jen-Hau Chen (GeroScience, 2026)

Green synthesized Cu2O/TiO2 nanotube heterojunction for pharmaceutical mineralization and simultaneous hydrogen evolution: mechanistic insight and toxicity assessment - Fang-Yu Liang; Dong-Ni Wu; Wan-Chun Lin; Yi-Ching Lin; Chia-En Tsai; Chia-Hua Lin; Wu-Xing Chen; Chia-Hung Chen; Yen-Ping Peng (Journal of Environmental Management, 2026)

Circular bioprocessing of bovine blood for peptide-based antimicrobial and antibiofilm agents - Gan Huey; Asif Ali Bhat; Bao-Hong Lee; Ming‐Kuei Shih; Li-Jung Yin; You-Lin Tain; Yu-Wei Chen; Yeu-Ching Shi; Chih-Yao Hou (Bioresource Technology, 2026)

Unraveling rainfall-induced accelerated slope deformation through the integration of GNSS, seismic, and hydrologic data in Lantai, Taiwan - Yan-Hong Chen; Ya-Ju Hsu; Hsin-Hua Huang; Kuo-Lung Wang; Rou-Fei Chen; Horng-Yue Chen; Jyr-Ching Hu; Chuen-Fa Ni; Kuo-Jen Chang; Chih-Yu Kuo (Landslides, 2026)
Studying deep-seated catastrophic landslides is challenging due to their complex geological conditions, slow and imperceptible movements, limited real-time monitoring, and difficulties in accurately assessing sliding behavior. We examine slope instability in a deep-seated landslide-prone area located in Lantai, Taiwan, by analyzing the temporal evolutions of slope movement and rainfall. Using a non-invasive automatic monitoring system that integrates the Global Navigation Satellite System, seismic velocity changes derived from ambient noise interferometry, as well as rainfall and groundwater-level records, we investigate rainfall-induced accelerated slope deformation in 2015–2024. Our findings show that acceleration events are triggered when rainfall lasts over 30 h and cumulative rainfall exceeds 200 mm at the study site. Multiple sliding events show a consistent temporal sequence, in which rainfall triggers an immediate dv/v decrease of 2–4%, followed by GNSS horizontal displacement typically in the range of ~10–30 mm within 1–2 days, and a delayed groundwater-level rise of about ~3 m occurring 4–5 days after peak GNSS displacement rate. This time lag suggests the initial slope acceleration is associated with pore-pressure increases within the landslide mass. The one-dimensional hydrological model successfully simulates rainfall infiltration into the groundwater system, enabling prediction of delayed groundwater responses. This integrated monitoring-modeling framework improves hazard assessment and early warning for rainfall-induced deep-seated landslides and is broadly applicable worldwide.

Efficacy of NEPA for prevention of chemotherapy induced nausea and vomiting in head and neck cancer patients receiving cisplatin-based chemotherapy - Tzer-Zen Hwang; Chih-Chun Wang; Chuan-Chien Yang; Ching-Feng Lien; Chien-Chung Wang; Yu-Chen Shih; Shyh-An Yeh; Tai-Heng Yeh; Meng-Che Hsieh (European Journal of Clinical Pharmacology, 2026)

Volatile Compounds from Endophytic PGPM Improve Copper Tolerance by Regulating Redox Balance in Cauliflower - Jing-Yu Chen; Tri-Phuong Nguyen; Chih-Cheng Lin; Ching-Han Chang; Hieng-Ming Ting; Ping-Fu Hou; Hao-Jen Huang (Journal of Plant Growth Regulation, 2026)

First complete coding sequence of ovine herpesvirus 2 from a malignant catarrhal fever case of Formosan sambar deer in Taiwan: Genomic characterization and molecular epidemiology - Ruei-Sheng Tsai; Shih-Te Chuang; Hau-You Tzeng; Fong-Yuan Lin; Ching-Yu Tseng; Yi-Chen Chen; Wei-Li Hsu (The Veterinary Journal, 2026)

Novel DUAL Z-SCHEME Bi2MoO6/SO3H@g-C3N4/ZnS photocatalyst enhanced by persulfate activation for rapid ofloxacin degradation: Integrated experimental and DFT studies - Imran Nasir Appau Zahir Hussain; Sanjay Ballur Prasanna; Po-Chun Chen; Yu-Chien Lin; Ching-Wei Tung; Ren-Jei Chung (Journal of Water Process Engineering, 2026)

Applying the iRIC Morpho2DH model to determine the effectiveness of check dams against debris flows - Zheng-Yi Feng; Philipp Marr; Tien-Chun Hsu; Ping-Hsuan Kuo; Yu-Po Lin; Ming-Chih Chuang; Ching-Mao Huang; Edoardo Carraro; Su-Chin Chen; Chen-Yu Chen; Thomas Glade (Landslides, 2026)

Comparative study of promising CaAl-LDH and conventional immobilizing agents in mitigating ecological and health risks associated with soil Pb contamination - Jianying Yu; Nan Wei; Haochen Fang; Yining Chen; Tengfei Guo; Qijia Zhang; Yangyang Chen; Jiahong Yu; Jianyu Zhang; Zeliang Han; Kaiqin Xu; Ching Yuan; et al. (Journal of Environmental Management, 2026)

A proof-of-concept study on green mining of seawater calcium via biochar interfaces for fluoride removal and carbon dioxide capture - TsingHai Wang; Zi-Ying Lu; Yun-Chen Sung; Chia-An Tsao; Jenn-Fang Su; Ching-Lung Chen; Chung-Yu Guan (Journal of Environmental Chemical Engineering, 2026)

Safety and toxicity assessment of Lactobacillus salivarius AP-32 with Probiotic potential in vivo and in vitro - Yu-Hsuan Chin; Yi-Wen Chen; Yen-Yu Huang; Ching-Min Li; Jia-Hung Lin; Yi-Wei Kuo; Chen-Yu Chen; Yen-Feng Lee; Cian-Dai Ciou; Ko-Chiang Hsia; Shin-Yu Tsai; Hsieh-Hsun Ho (Food and Chemical Toxicology, 2026)

Methotrexate-loaded FeAuGd nanoparticles for synergistic magnetic-hyperthermia and chemotherapy - Kayalvizhi Samuvel Muthiah; Lenin Subramanian; Yen-Lin Chen; Udesh Dhawan; Yu-Chien Lin; Ching-Li Tseng; Ren-Jei Chung (Chemical Engineering Journal, 2026)

Prioritizing key determinants of hematite photocatalysis through structure – Property contour mapping and statistical correlation analysis - TsingHai Wang; Ching-Lung Chen; Wei-Fan Kuan; Wei-Tong Li; Ching-Yao Ke; Tzu-Han Lin; Chung-Yu Guan; Huei-Ru Fuh (Process Safety and Environmental Protection, 2026)

Improvement of indoor air quality and health effects in COPD patients in a heavy industrial area - Jia Lin Zhang; Yi Ting Chang; Ching Yu Hsiao; Chung-Shin Yuan; Yen-Ping Peng; Da Wei Wu; Huang-Chi Chen; Jia-Yu Kuo; Huai-Lei Juan; Pei-Shih Chen (Environmental Research, 2026)

Metabolomics-based investigation of PFOS-induced molecular perturbations across multiple rat organs - Tzu-Hsin Yen; Sheng-Han Lee; Hao-Jan Liang; Zou-Xiao Huang; Chi-Tsung Chen; Christopher Li; Ching-Yu Lin (Environmental Toxicology and Pharmacology, 2026)

Aldehyde dehydrogenase 2 mitigates acrolein-driven ferroptosis to preserve kidney function - Yu-Ming Kuo; Shiu-Dong Chung; Jui-Ting Chang; Hui-Min Yang; Chieh-Chen Lee; Chih-Ching Lin; Hsiang-Tsui Wang (Environmental Pollution, 2026)

Coupled oxygen and nitrogen defect sites in Co-N4-coordinated frameworks facilitate stepwise CO2 methanation - Pin-Yu Liu; Sheng-Xiang Chou; Wei-Tse Sun; Hsin-Han Chen; Cheng-Hung Tsai; Yen-Lin Lai; Yu-Cheng Shao; Chi-Liang Chen; Yu-Ching Huang; Yun-Wei Chiang; Bo-Hong Liu; Chia-Hsin Wang; et al. (Chemical Engineering Journal, 2026)

Spatio-temporal dynamics of fish assemblages at an offshore wind farm and a comparison with mature artificial reefs - Kwang Tsao Shao; Ching Han Chang; Ching Yi Chen; Lin Tai Ho; Yi Ta Shao; Hsin-Chieh Chiang; Wei-Ning Lee; Hsien Ju Tsai; Tien-Yu Huang; Chun-Yu Chang (Frontiers in Marine Science, 2026)
Introduction Offshore wind farms (OWFs) are vital for sustainable energy. The underwater foundations of those wind turbines provide a complex structure that creates new habitats and attracts fishes. However, whether OWFs had the same ecological function as purpose-built artificial reef (AR) and how they alter the original fish community remain unclear. Methods To evaluate the spatial and temporal variations in fish assemblages, we conducted a multi-part investigation at the Formosa Wind Farm, located off the coast of Miaoli County, Taiwan. Temporal changes were assessed through SCUBA surveys at turbine foundations in 2017, 2018, and 2025, with the 2025 data allowing for a direct comparison with the nearby existing artificial reefs. To assess spatial effects, pole-and-line surveys were conducted from Apr to Oct in 2024 and 2025 at varying distances from the turbines. Results Our investigation documented 86 species of reef-associated fishes exclusively within 50 m of turbine foundations; none were caught in the surrounding sandy areas or documented in pervious fishery records. The results demonstrated that fish assemblages around the turbine piles changed successively over the years. Although the species composition in 2025 differed between the OWF and the established AR sites, key ecological metrics such as species richness, diversity, and trophic structures showed no significant differences. Discussion These findings demonstrated that the underwater structure of offshore wind turbines can function as AR, creating novel reef habitats and supporting reef-associated fish community within a finite spatial extent. Overall, OWFs may provide ecological benefits in addition to renewable energy, highlighting their potential role in balancing energy development with marine conservation.

Environmental DNA metabarcoding enriches the conventional survey of a high diverse fish community in the Dongsha atoll - You-Chen Liu; Yi-Ching Yang; Kang-Ning Shen; Chun-Huo Chiu; Te-Yu Liao (Frontiers in Marine Science, 2026)
To effectively conserve coral reef ecosystems, it is essential to monitor changes in fish fauna using minimally invasive methods. In this study, we conducted a fish survey in the Dongsha Atoll using eDNA metabarcoding. Analyzing 37 sequencing units from 26 water samples collected across 12 sites from May 2017 to September 2018, we identified 421 species from 79 families. Among these, 192 species had not been recorded in previous conventional surveys. Some of these newly recorded species are fast-swimmers, while others may be larvae or eggs, which are challenging to observe visually. However, 68% of species documented in previous records were not detected in our study. This limitation is likely due to insufficient samplings, primer specificity, fish characteristics, and rapid DNA degradation in the dynamic physical and chemical conditions (e.g., temperature, pH) of the coastal environment. Despite that eDNA metabarcoding cannot capture the full range of species within the atoll, it effectively complements visual census surveys by enriching our understanding of the diverse fish community in marine habitats.

Reef fish assemblages show limited response to giant clam density and restocking - Nathan W. Price; Yan-Zhen Meng; Wen-Yuan Zhang; Jinn-Shing Weng; Ching-Min Yang; Kao-Sung Chen; Joseph Heard; Wei-Chen Tung; Yu-De Pei; Colin Kuo-Chang Wen (Regional Studies in Marine Science, 2026)

Emerging trends and clinical challenges in AI-enhanced emotion diagnosis using physiological data - Ying-Ying Tsai; Guan-Lin Wu; Yu-Jie Chen; Yen-Feng Lin; Ju-Yu Wu; Ching-Han Hsu; Lun-De Liao (Medical & Biological Engineering & Computing, 2026)

Potential anti-H1N1 schitriterpenoids from Kadsura japonica L. vines - Hung-Tse Huang; Chun-Tang Chiou; Yu-Chi Lin; Li-Jie Zhang; Chih-Hua Chao; Ping-Jyun Sung; Jih-Jung Chen; Tsung-Lin Li; I-Wen Lo; Chia-Ching Liaw (Phytochemistry, 2025)

Uncovering AphBvp-mediated regulation of PirAvp/PirBvp toxins and biofilm formation in AHPND causing Vibrio parahaemolyticus - Michael Eniola Ayenero; Ramya Kumar; Han-Ching Wang; Phuoc Thien Le; Yu-Hsuan Chen; Chu Fang Lo; Shin-Jen Lin; Hao-Ching Wang (Fish & Shellfish Immunology, 2025)

Mitochondrial pyruvate carrier proteins mediate host-pathogen interactions during WSSV infection in shrimp - Yu-Chen Lin; Saengchan Senapin; Pakkakul Sangsuriya; Han-Ching Wang (Fish & Shellfish Immunology, 2025)

Alkylammonium ligands-driven perovskite lattice engineering for white perovskite nanocrystals single emitters - Jean-Sébastien Bénas; Zhen-Li Yan; Wei-Cheng Chen; Chu-Chen Chueh; Jing-Yan Wu; Wei-Wen Chen; Fang-Cheng Liang; Erdi Akman; Yu-Jung Lu; Yen-Yu Wang; Ja-Hon Lin; Ye Zhou; et al. (Chemical Engineering Journal, 2025)

Unleashing instant on-site naked-eye detection by a portable NIR-SPR platform with organic upconversion - Li-Chen Su; Xin-Hui Wang; Chun-Jen Shih; Zhi-Hao Huang; Ying-Feng Chang; Chen-Kai Chang; Chi-Yun Wang; Yu-Ching Huang; Shun-Wei Liu (Chemical Engineering Journal, 2025)

Antioral cancer effects of ginger derivative 3-HDM exert oxidative stress-associated apoptosis and DNA damage - Kuan-Liang Chen; Hsin-I Lu; Ching-Yu Yen; Chung-Yi Chen; Tsu-Ming Chien; Jiiang-Huei Jeng; Bing-Hung Chen; Hsueh-Wei Chang (Molecular Biology Reports, 2025)

Development and validation of a five-channel multiplex LC−ESI−MS/MS method for the quantification of carboxylic acids in urine - Wan-Hui Lu; Ju-Yu Chen; Te-I Weng; Ching-Hua Kuo; Guan-Yuan Chen (Analytica Chimica Acta, 2025)

Social-ecological memories as references for biodiversity restoration and conservation action in coastal community - Chia-Hsuan Hsu; Yu-Wen Wu; Jiefeng Kang; Hung-Kai Chiu; Mei-Ching Li; Wei-Ting Chen (Marine Pollution Bulletin, 2025)

Real-world emissions and total output from fishing vessels in Taiwan - Po-Yen Chien; Chia-Hsiang Lai; Wu-Xing Chen; Chia-Hung Chen; Chia C. Wang; Amila Kasun Abeysinghe; Yi-Ching Lin; Tsai-Jung Yen; Hsiang-Ying Wu; Yu-Lun Tseng; Pei-Shih Chen; Yen-Ping Peng (Transportation Research Part D: Transport and Environment, 2025)

Empagliflozin attenuates sorafenib-promoted renal ferroptosis and inflammation by targeting cyclooxygenase-2/prostaglandin E2 axis - Ming-Kai Tsai; Wen-Chin Lee; Shih-Chung Huang; Chao-Cheng Huang; Yi-Chen Wang; Chien-Han Yuan; Chih-Chiang Wang; Ching-Han Liu; Nan-Chieh Huang; Yi-Chen Chang; Cheng-Chieh Fang; Bi-Wen Yeh; et al. (Toxicology and Applied Pharmacology, 2025)

Anaerobic Fe(II) bio-oxidation by Cyanidiophyceae to enhance As(III) removal: A novel and efficient biological material toward resilient remediation - Nhu Anh Thi Than; Liang Ching Hsu; Yu-Hsien Chen; Kamonchanok Huangmee; Chun-Chieh Wang; Heng Yi Teah; Yu-Min Tzou; Yen-Lin Cho; Yu-Ting Liu (Chemical Engineering Journal, 2025)

Discovery of a new 1-monoglyceride from Streptomyces albogriseolus JM128 symbiotic with Lendenfeldia sponge - Yun-Ting Zeng; Chia-Ching Liaw; Yu-Chi Lin; Su-Ying Chien; You-Ying Chen; Li-Guo Zheng; Chih-Yin Huang; Hsi-Wen Sun; Ping-Jyun Sung (Phytochemistry Letters, 2025)

Unveiling Unusual Ecofunctional Traits of Endozoicomonas Species Through Comprehensive Comparative Genomics - Sim Lin Lim; Ching‐Hsiang Chin; Yu‐Jing Chiou; Ming‐Tsung Hsu; Pei‐Wen Chiang; Hsing‐Ju Chen; Yung‐Chi Tu; Wen‐Shyong Tzou; Sen‐Lin Tang (Environmental Microbiology, 2025)
Endozoicomonas is an omnipresent marine bacterial genus, associated with various marine organisms, that contributes to host health, nutrient cycling and disease resistance. Nonetheless, its genomic features remain poorly characterised due to a paucity of high‐quality genomes. In this study, we sequenced 5 novel Endozoicomonas strains and re‐sequenced 1 known strain to improve genomic resolution. By integrating these 6 high‐quality genomes with 31 qualified published genomes, our pan‐genomic analysis revealed variation in genetic traits among clades. Notably, Endozoicomonas lacks quorum‐sensing capabilities, suggesting resistance to quorum quenching mechanisms. It also lacks the capacity to synthesise and transport vitamin B12, indicating that it does not supply this nutrient to holobionts. Remarkably, Endozoicomonas genomes encode 92 identified giant proteins (15–65 kbp). These proteins cluster into three major groups associated with antimicrobial peptide synthesis, exotoxin production and cell adhesion. Additionally, we found that Endozoicomonas has acquired prophages from diverse sources via infection or other types of gene transfer. Notably, CRISPR‐Cas sequences suggest evolutionary trajectories independent of both prophage acquisition and phylogenetic lineage, implying potential geographic influences or environmental pressures. This study provides new insights into the genomic diversity of Endozoicomonas and its genetic adaptations to diverse hosts.

Gallium maltolate and cisplatin co-treatment effectively targets triple-negative breast cancer in spheroid and mouse models - Ya-Wen Yang; Yu-Chen Hsieh; Ching-Yu Liu; Chun-Kai Pan; Zi-Yu Pan; Kai-Yin Lo (Toxicology and Applied Pharmacology, 2025)

Causes, emission characteristics, and health risks of persistent free radicals and reactive oxygen species in PM2.5 produced by smoldering incense - Yu-Chieh Wang; Bo-Yu Chen; Yen-Hsien Li; Tzu-Hsien Tseng; Chon-Lin Lee; Wei-Min Ching (Atmospheric Pollution Research, 2025)

Adaptive fluoride removal across concentration scales: Potential roles of microbial and acicular gypsum interactions in nitrogen and phosphate cycling - Ying-Liang Yu; Wei-Han Lin; Rao Y. Surampalli; Ssu-Ching Chen; Chih-Ming Kao (Journal of Hazardous Materials, 2025)

Enhanced removal of antimony, arsenic and cadmium by bone char in co-contaminated aqueous systems: A lattice level mechanistic understanding - Prakash C. Loni; Biqing Liang; Ching-Yu Chiang; Yao-Chang Lee; Jagat Rathod; Ci-Hong Ciou; Pei-Hua Wu; Wei-Hsin Chen (Journal of Environmental Chemical Engineering, 2025)

Sequential slot-die coating of perovskite solar cell modules under ambient conditions with precise phase-transition control - Chia-Feng Li; Shih-Han Huang; You-Ren Chen; Hou-Chin Cha; Ssu-Yung Chung; Yu-Hung Hsiao; Feng-Yu Tsai; Yu-Ching Huang (Chemical Engineering Journal, 2025)

Development and Evaluation of a Dual-Mode Cold Atmospheric Plasma System for Stage-Specific Wound Healing Applications - Ching-Yuan Lin; Dong-Jin Li; Yu-Shen Chen; Chia-Wei Hsu; Mohd Yaqub Khan; Ming-Chen Wang (Journal of Medical and Biological Engineering, 2025)

Enhanced Hair Growth Through Transdermal Delivery of Bacopa Monnieri Extract Using a Needle-Free Supersonic Atomizer - Yu-Chiuan Wu; Yi-Ping Lin; Ching-Yi Chang; Hsia-Ying Cheng; Tien-Huei Chu; Chien-Chih Chen; Shyh-Ming Kuo (Journal of Medical and Biological Engineering, 2025)

Palmitic acid and lipopolysaccharide induce macrophage TNFα secretion, suppressing browning regulators and mitochondrial respiration in adipocytes - Tsui-Chun Tsou; Szu-Ching Yeh; Feng-Yuan Tsai; Pei-Yu Chen (Toxicology and Applied Pharmacology, 2025)

Polycyclic aromatic hydrocarbon-aryl hydrocarbon receptor signaling regulates chronic inflammation in lung-gut axis - Tzu-Yu Cheng; Ching-Shan Luo; Po-Hao Feng; Kuan-Yuan Chen; Chih-Cheng Chang; Nguyen Van Hiep; Yueh-His Chen; Yun-Kai Yeh; Sheng-Ming Wu (Toxicology and Applied Pharmacology, 2025)

Microplastic-induced hypertension in rats: A two-hit model exploring oxidative stress and gut microbiota - Yu-Chun Cheng; Wei-Ling Chen; Hong-Ren Yu; Ching-Yi Tsai; Jiunn-Ming Sheen; Mao-Meng Tiao; Chien-Ning Hsu; You-Lin Tain (NanoImpact, 2025)

Response and recovery times of vegetation productivity under drought stress: Dominant factors and relationships - Chengyun Wang; Jie Chen; Sung-Ching Lee; Lihua Xiong; Tianhua Su; Qian Lin; Chong-Yu Xu (Journal of Hydrology, 2025)

A potential closed-loop reutilization of iron sludge for wastewater treatment through the solid state reaction with spent coffee grounds - Kun Qin; TsingHai Wang; Wei-Tong Li; Zi-Ying Lu; Cheng-Yu Li; Wei-Fan Kuan; Jenn-Fang Su; Ching-Lung Chen (Process Safety and Environmental Protection, 2025)

Fabrication of sesamin-loaded sodium caseinate nanoparticles: Insight to characterization, in vitro digestion, and molecular docking analysis - Wan-Yi Liu; Tzu-Yu Chen; Yun-Shan Hsieh; Yung-Yi Cheng; Shiou-Ling Li; Li-Ching Chang; Yu-Tse Wu (Food Bioscience, 2025)

Pixel array-based urine biosensor for detection of trimethylamine N-oxide and glucose for early detection of diabetic kidney disease - Mei-Ching Yu; Chi-Jen Lo; Wei-Cheng Lin; Wei-Lun Yen; Yun-Yu Hsieh; Bing-Hong Chen; Fu-Sung Lo (Analytica Chimica Acta, 2025)

Prenatal melatonin reprograms liver injury in male pups caused by maternal exposure to a high-fat diet and microplastics - Yu-Jen Chen; Hong-Ren Yu; Ching-Chou Tsai; Mao-Meng Tiao (Apoptosis, 2025)

BTEX exposure and metabolite levels in Taiwan schoolchildren near petrochemical areas - Wei-shan Chin; Ching-chun Huang; Yu-cheng Chen; Jing-fang Hsu; Chih-Da Wu; Pinpin Lin; Pau-chung Chen; Yue Leon Guo (International Journal of Hygiene and Environmental Health, 2025)

Preliminary analysis of landslides induced by the 3 April 2024 Mw 7.4 Hualien, Taiwan earthquake - Yi Chen; Chuang Song; Zhenhong Li; Bo Chen; Chen Yu; Jyr-Ching Hu; Xingmin Cai; Shuang Zhu; Qianwen Wang; Yixin Ma; Changjun Gu; Suju Li; et al. (Landslides, 2025)

ONC201 exerts oncogenic effects beyond its mitochondria-disturbing role in neuroblastoma subsets - Jyun-Hong Jiang; Yu-Han Lin; Pei-Lin Liao; Ting-Ya Chen; Hui-Ching Chuang; Chao-Cheng Huang; Wen-Ming Hsu; Jiin-Haur Chuang; Wei-Shiung Lian (Journal of Molecular Medicine, 2025)
Neuroblastoma (NB) is a formidable challenge in pediatric oncology due to its intricate molecular landscape, necessitating multifaceted therapeutic approaches. ONC201 is an imipridone antibiotic compound with a promising drug candidate leveraging its potent anticancer properties against the mitochondrial proteases ClpP and ClpX. Despite demonstrating early clinical promise, particularly in MYCN -amplified NB, its efficacy in non- MYCN -amplified NB remains a subject worthy of investigation. In this study, we extended the coverage of ONC201 to treat non- MYCN -amplified NB, and our data implicated ONC201’s inability to reduce tumor growth in animal models harboring SK-N-AS or SK-N-FI cell lines. Interestingly, ONC201 induced the expression of oncogenic markers c-Myc and LGR5 while downregulating the tumor suppressor ATRX. While it fails to attenuate tumor neovascularization in non- MYCN -amplified NB xenografts, its effectiveness differs from that of its MYCN-amplified counterpart. Rho zero (ρ0)-SK-N-AS cells treated with ONC201 showed comparable observed trends in parental SK-N-AS cells, including LGR5 upregulation and ATRX downregulation, suggesting that ONC201’s multifaceted actions extend beyond mitochondrial targets. Our elucidation highlights the need to discern molecular signatures when deploying ONC201 monotherapy against NB, which lacks MYCN- amplification.

4-Anilinoquinolinylchalcone derivatives mediate antifibrotic effects through ERK/MRTF—a signaling pathway crosstalk - Padhmavathi Selvam; Chih Hua Tseng; Ching Tung Wang; Yu-Yo Sun; Yeh-Long Chen; Yu-Tse Kao; Hans-Uwe Dahms; Chih Mei Cheng (Environmental Science and Pollution Research, 2025)

Junceellolide Q, a new polyacetoxybriarane from the delicate sea whip octocoral Junceella fragilis - Yih-Gang Goan; Mingzi M. Zhang; Lun Kelvin Tsou; Zhi-Hong Wen; Chia-Ching Liaw; Yu-Chi Lin; Su-Ying Chien; Yu-Jen Wu; Jih-Jung Chen; Hai Nhat Do; Pei-Luen Jiang; Ping-Jyun Sung (Phytochemistry Letters, 2025)

Effects of humidity on photocatalytic oxidation of elemental mercury by rGO-modified CeO2/TiO2: Kinetic analysis and experimental exploration - Ji-Ren Zheng; Chung-Shin Yuan; Ting-Yu Chen; Ching-Ching Hsu; Chung-Hsuang Hung; Huazhen Shen (Journal of Environmental Chemical Engineering, 2025)

Boosting anode interfacial stability in All-Solid-State lithium hybrid batteries with MCMB-Modified stainless steel current collector - Abebe Taye Fenta; Yosef Nikodimos; Semaw Kebede Merso; Ayenew Meniber; Misganaw Adigo Weret; Kassie Nigus Shitaw; Bereket Woldegbreal Taklu; Felika Valencia; Tsung-I Yeh; Chia Lung Hsieh; Chia-Yu Chang; Ya-Jun Liu; et al. (Chemical Engineering Journal, 2025)

Displacement evolution of failure and non-failure sliding rock slopes - Hsien-Li Kuo; Guan-Wei Lin; Ting-Yu Lin; Che-Hsin Liu; Chung-Ray Chu; Chih-Hsin Chang; Ching-Weei Lin; Hongey Chen (Landslides, 2025)

Kirenol ameliorates endotoxin-induced acute lung injury by inhibiting the ERK and JNK phosphorylation–mediated NFκB pathway in mice - Frank Cheau-Feng Lin; Shih-Pin Chen; Sheng-Chien Lin; Ching-Chi Tseng; Stella Chin-Shaw Tsai; Yu-Hsiang Kuan (Inflammopharmacology, 2025)

Artificial digestion represents the worst-case scenario for studying nanoplastic fate in gastrointestinal tract - Giselle Lee; Ya-Jhu Jhang; Yu-Tung Jhang; Yen-Chen Chang; Hui-Wen Chang; Chun-Yu Chuang; Yung-Kun Chuang; Ching-Wei Lin; I-Lun Hsiao (Journal of Hazardous Materials, 2025)

Proximity to petrochemical industry and risk of childhood asthma occurrence - Shih-Chun Pan; Wei-Shan Chin; Ching-Chun Huang; Yu-Cheng Chen; Chih-Da Wu; Chin-Yu Hsu; Pinpin Lin; Pau-Chung Chen; Yue Leon Guo (International Journal of Hygiene and Environmental Health, 2025)

Safety evaluation of Limosilactobacillus fermentum PS150 for use as a commercial psychobiotic - Li-Hao Cheng; Chien-Chen Wu; Chin-Lin Huang; Yu-Hsuan Wei; Pei-Jun Wen; Shih-Hau Chiu; Chien-Chi Chen; Ching-Ting Lin; Po-Lin Liao (Food and Chemical Toxicology, 2025)

Interactions between environmental pollutants and gut microbiota: A review connecting the conventional heavy metals and the emerging microplastics - Xiaochen Chen; Zengdi Zhang; Yushiang Hsueh; Chunpeng Zhang; Jianying Yu; Junyu Zhu; Jia Niu; Naiyi Yin; Jianyu Zhang; Xiaoyu Cui; Xianhua Liu; Kaiqin Xu; et al. (Environmental Research, 2025)

ZFP36L1 and ZFP36L2 reduce cyclin D1 expression by decreasing expression of E2F1 and long 3’UTR isoform of CCND1 transcripts - Tze-Sian Chan; Kun-Lin Lee; Ching-Sheng Hung; Hsin-Pei Chiang; Chia-Chen Chung; Yu-Chih Liang (Molecular and Cellular Biochemistry, 2025)

Challenges and limitations of applying the flux variance similarity (FVS) method to partition evapotranspiration in a montane cloud forest - Ching-Hung Shih; Ray G. Anderson; Todd. H. Skaggs; Jehn-Yih Juang; Yi-Ying Chen; Yi-Shin Jang; Rong-Yu Gu; Cho-Ying Huang; Min-Hui Lo (Agricultural and Forest Meteorology, 2025)

Correction: CCL4 contributes to aging related angiogenic insufficiency through activating oxidative stress and endothelial inflammation - Ting-Ting Chang; Liang-Yu Lin; Ching Chen; Jaw-Wen Chen (Angiogenesis, 2025)

Ambient stable ZnBr2-assisted lead-free perovskite for enhanced piezoelectricity of polyvinylidene fluoride in versatile piezo-phototronic applications - Manikandan Venkatesan; Wei-Chun Lin; Wei-Cheng Chen; Jayashree Chandrasekar; Yu-Hang Huang; Kai-Wei Lin; Zih-Syuan Syu; Ja-Hon Lin; Wei-Hung Chiang; Wei-Ren Liu; Ye Zhou; Chi-Ching Kuo (Chemical Engineering Journal, 2025)

Highly active Cu-embedded in magnetic carbon nanofibers for the reduction of 4-nitrophenol - Ching-Shiun Chen; Tse-Ching Chen; Kai-Lin Chiu; Cheng-Rong Hsing; Li-Yu Wang; Chia-Min Yang; Chih-Wen Pao; Chi-Liang Chen (Chemical Engineering Journal, 2025)

Myriscagayanone C, a new compound from the fruit of myristica cagayanensis, inhibits fMLP-induced respiratory bursts by specifically preventing Akt translocation in human neutrophils - Hsiang-Ruei Liao; Chen-Lung Chen; Yu-Yao Kao; Fu-Chao Liu; Ching-Ping Tseng; Jih-Jung Chen (Chemico-Biological Interactions, 2025)

Digital transformation of mental health therapy by integrating digitalized cognitive behavioral therapy and eye movement desensitization and reprocessing - Ju-Yu Wu; Ying-Ying Tsai; Yu-Jie Chen; Fan-Chi Hsiao; Ching-Han Hsu; Yen-Feng Lin; Lun-De Liao (Medical & Biological Engineering & Computing, 2025)

Using Gaussian Mixture Model Clustering for the Automated Segmentation of Cerebral Arteriovenous Malformations in Magnetic Resonance Images - Ting-Yu Lin; Cheng‑Chia Lee; Yu-Wei Chen; Hsiu-Mei Wu; Ching-Jen Chen; Huai-Che Yang; Syu-Jyun Peng (Journal of Medical and Biological Engineering, 2025)

Analysis of serotype distribution and characteristics of nonhemolytic and nonpigmented strains among group B Streptococcus isolates in a southern Taiwan local hospital - Hui-Fang Cheng; Zhe-Yu Kuo; Ching-Chiang Lin; Ho-Feng Chen; Horng-Ren Lo; Huey-Wen Shyu; Yi-Fen Wang (European Journal of Clinical Microbiology & Infectious Diseases, 2025)

The difference in roaming behavior between owned and unowned dogs in a satoyama landscape area - Tsung-Han Kuo; Gau-Ming Chang; Pin-Huan Yu; Wei-Hsuan Chen; Shih-Ching Yen (Applied Animal Behaviour Science, 2025)

Enhanced nano-LC-MS for analyzing dansylated oral cancer tissue metabolome dissolved in solvents with high elution strength - Ya-Ju Hsieh; Cheng-Yu Hung; Yi-Ting Chen; Yu-Tsun Lin; Kai-Ping Chang; Wei-Fan Chiang; Chih-Yen Chien; Chih-Ching Wu; Liang Li; Jau-Song Yu; Kun-Yi Chien (Analytica Chimica Acta, 2025)

The Impact of Administrative Districts and Urban Landscape on the Dispersal of Aedes aegypti via Genetic Differentiation - Chin‐Gi Huang; Yi‐Cheng Tseng; Tsung‐Han Yu; Hui‐Ching Cheng; Tsung‐Ju Tsai; Jou‐Hsin Ting; Hsin‐Yi Ho; Ya‐Zhe Lee; Yen‐Chieh Chiu; Yu‐Ting Huang; Ting‐Chun Shih; Hsiang‐Yu Hsiao; et al. (Molecular Ecology, 2025)
Mosquito‐borne diseases affect millions and cause numerous deaths annually. Effective vector control, which hinges on understanding their dispersal, is vital for reducing infection rates. Given the variability in study results, likely due to environmental and human factors, gathering local dispersal data is critical for targeted disease control. To analyse the spread and differentiation of Aedes aegypti in southern Taiwan, we established a dengue vector monitoring network in Southern Taiwan's cities. This network employed GPS‐equipped ovitraps to gather eggs that were subsequently hatched in the laboratory and genotyped using genome‐wide SNP markers. From 168 individuals, we identified 757,238 SNPs for detailed analysis. The estimated effective dispersal distance was 154 m (95% CI: 126–180 m), consistent with prior mark‐release‐recapture (MRR) estimates. We discovered that geographic isolation significantly influences genetic differentiation at larger scales, such as between cities, whereas its correlation with genetic distances is considerably weaker at smaller scales, like within cities. This is likely due to the urban landscape in Taiwan, characterised by narrow roads and densely packed buildings, which facilitates extensive dispersal of Ae. aegypti. In evaluating potential barriers to Ae. aegypti dispersal, we found that roads had no significant impact, whereas administrative districts accounted for 4.8% of the population differentiation ( p −4 ). Surprisingly, this variation aligns with the effects of district‐specific mosquito control measures implemented at the municipal level. These findings highlight the complex interplay between urban landscapes, administrative measures and Ae. aegypti dispersal, emphasising the need for implementing targeted control strategies that consider these local dynamics.

Tidal currents and atmospheric inorganic nitrogen contribute to diurnal variation of dissolved nutrients and chlorophyll a concentrations in Mirs Bay, Hong Kong - Ho Wen Lo; Xu Yu; Hanzhe Chen; Wai Ching Chu; Nga Man Chung; Sze Wing Lau; Jinjian Li; Shumin Liang; Kezheng Liao; Henry Charles James Thomas; Ziyan Wang; Zijing Zhang; et al. (Regional Studies in Marine Science, 2025)

Dual functionality of carbazole-based phosphonic acid molecular additives realizes efficient hole transport layer-free perovskite light-emitting diodes - Yin-Ti Lai; Chiung-Han Chen; Ming-Hsuan Yu; Hsing-Yu Kuo; I-Chih Ni; Bi-Hsuan Lin; Hobeom Kim; Chi-Ching Kuo; Yu-Jung Lu; Chu-Chen Chueh (Chemical Engineering Journal, 2025)

Deep learning in the advanced core sample porosity determination with XCT image - Hung-Yu Wu; Ching-Li Kuo; Chen-Yi Lin; Wei-Ta Chu (Earth Science Informatics, 2025)

Bio-inspired sustainable electrospun quantum nanostructures for high quality factor enabled face masks and self-powered intelligent theranostics - Loganathan Veeramuthu; Ren-Jie Weng; Wei-Hung Chiang; Archana Pandiyan; Fu-Jie Liu; Fang-Cheng Liang; G. Ranjith Kumar; Hua-Yi Hsu; Yu-Ci Chen; Wen-Yinn Lin; Yao-Chun Tang; Wan-Rong Lin; et al. (Chemical Engineering Journal, 2024)

The Association Among Urinary Di-(2-ethylhexyl) Phthalate Metabolites, Serum Lipid Profiles, and Serum Apoptotic Microparticles in a Young Taiwanese Population - Chien-Yu Lin; Sandy Huey-Jen Hsu; Ching-Way Chen; Chikang Wang; Fung-Chang Sung; Ta-Chen Su (Exposure and Health, 2024)

Effect of a tropical cyclone on the pelagic ecosystem of a continental shelf - Chung‐Chi Chen; Chih‐hao Hsieh; Yu‐Hsin Cheng; Wei‐Jen Huang; Wen‐Chen Chou; Fuh‐Kwo Shiah; Gwo‐Ching Gong; Tzong‐Yueh Chen (Limnology and Oceanography, 2024)
This study aimed to comprehend the effects of Typhoon Maria on the pelagic ecosystem in the southern East China Sea. Shipboard measurements were conducted at eight sampling stations before (2–4 d) and after (3–6 d) the typhoon, which enabled the evaluation of the potential impacts of the typhoon on this pelagic ecosystem, with particular focus on carbon dynamics. Following the typhoon's passage, there was a slight drop in sea surface temperature. The response of the variables to the typhoon, however, exhibited variations at different sampling stations. For further analysis, t ‐tests compared variables, while type II regression assessed the linear correlation between two variables. Overall, during the post‐typhoon period, concentrations of nitrate, chlorophyll a , primary production, bacterial biomass and production, plankton community respiration, and abundance of large phytoplankton (> 2 μ m) and the relative abundance of picophytoplankton among larger‐sized picoeukaryotes were higher compared to the pre‐typhoon period. The mean value of fugacity of CO 2 was similar to or slightly lower than pre‐typhoon period. Although the typhoon‐induced vigorous primary production might have absorbed a significant amount of CO 2 , the decrease in fugacity of CO 2 could have been offset by the plankton community respiration. The findings suggest that the typhoon enhanced physical disturbance and increased water column mixing, which, in turn, augmented nutrient availability and promoted plankton growth in the shallow water column. Overall, this study sheds light on the complex interactions between typhoons and marine ecosystems and highlights the importance of further investigating these phenomena to better understand their ecological implications.

Comprehensive evaluation of the nephrotoxicity of carbon quantum dots: Effects of the surface charge - Pei-Luen Jiang; Yan-Yu Hong; Lingyan Yang; Han-Jia Lin; Chih-Ching Huang; Yan-Hua Chen; Chia-Hua Lin; Yi-Chun Chen (Chemosphere, 2024)

Development of modified MgO/biochar composite for chemical adsorption enhancement to cleanup fluoride-contaminated groundwater - Ying-Liang Yu; Chiann-Yi Chen; Chathura Dhanasinghe; Francis Verpoort; Rao Y. Surampalli; Ssu-Ching Chen; Chih-Ming Kao (Journal of Environmental Management, 2024)

Rational design of stable Cu and AuCu nanoparticles for investigations of size-enhanced SERS applications - Kuan-Wen Liu; Pei-Yu Sie; Jing-Yin Huang; Hsi-Ying Chen; Yi-Lun Chen; Yu-Ching Lin; Mei-Yi Liao (Analytica Chimica Acta, 2024)

Development of Quantitative Norms for Normal Lung Uptake Based on Three-Dimensional Gallium-67 Single Photon Emission Computed Tomography/Computed Tomography - Tzyy-Ling Chuang; Wei-Lin Li; Yu-Ching Hs; Jyh-Cheng Chen; Yuh-Feng Wang (Journal of Medical and Biological Engineering, 2024)
Purpose Gallium-67 (Ga-67) lung scans assess alveolitis and interstitial lung disease, with Ga-67 accumulation correlating with inflammation intensity as seen in lung biopsy sections. Both semi-quantitative and quantitative methods have been used, with the latter providing an inflammatory activity index linked to lung lavage and histopathological scores. However, differing reference points result in varying outcomes. This study aimed to establish standard Ga-67 index parameters using semi-quantitative analysis and a linear regression model based on planar and SPECT/CT images. Methods Twenty subjects without lung disease received a 5–6 mCi Ga-67 injection via the ankle. Both planar and SPECT/CT images were analyzed, with semi-quantitative values assessed using GraphPad Prism 9.5.1. Results Compared to planar images, SPECT/CT acquisitions for the lung-to-arm uptake ratio proved the most reliable indicator for assessing lung inflammation. Increased lung Ga-67 uptake was defined as greater than 2 standard deviations from the average Ga-67 uptake for healthy subjects. The normal range was 0.065 ± 0.049 for the right side and 0.076 ± 0.070 for the left side. Conclusion Lung-to-arm ratios in SPECT/CT images are more accurate than those in planar images. This method should be adopted as a standard clinical practice, providing more reliable diagnostic information and improving patient management. Future studies should compare patients without lung disease to those with lung disease to determine the diagnostic benefit of these norms.

Recursive analytical solution for nonequilibrium multispecies transport of decaying contaminant simultaneously coupled in both the dissolved and sorbed phases - Yu-Chieh Ho; Heejun Suk; Ching-Ping Liang; Chen-Wuing Liu; Thu-Uyen Nguyen; Jui-Sheng Chen (Advances in Water Resources, 2024)

The impact of flooding from the Minjiang River on the succession of harmful algal blooms (HABs) caused by diatoms in China's offshore waters - Yun-Chi Lin; Ya-Han Nien; Kuo-Ping Chiang; Chien-Pang Chin; Wei-Ting Chen; Gwo-Ching Gong; Wen-Chen Chou; Chi-Yu Shih; Kuo-Shu Chen (Marine Pollution Bulletin, 2024)

Enhancing dye degradation in darkness: The role of SnO2 nanorod clusters in flexocatalysis - Nai-Jen Chang; Yu-Ching Chen; Sz-Nian Lai; Jyh Ming Wu (Chemical Engineering Journal, 2024)

Predicting ischemic stroke patients’ prognosis changes using machine learning in a nationwide stroke registry - Ching-Heng Lin; Yi-An Chen; Jiann-Shing Jeng; Yu Sun; Cheng-Yu Wei; Po-Yen Yeh; Wei-Lun Chang; Yang C. Fann; Kai-Cheng Hsu; Jiunn-Tay Lee (Medical & Biological Engineering & Computing, 2024)
Accurately predicting the prognosis of ischemic stroke patients after discharge is crucial for physicians to plan for long-term health care. Although previous studies have demonstrated that machine learning (ML) shows reasonably accurate stroke outcome predictions with limited datasets, to identify specific clinical features associated with prognosis changes after stroke that could aid physicians and patients in devising improved recovery care plans have been challenging. This study aimed to overcome these gaps by utilizing a large national stroke registry database to assess various prediction models that estimate how patients’ prognosis changes over time with associated clinical factors. To properly evaluate the best predictive approaches currently available and avoid prejudice, this study employed three different prognosis prediction models including a statistical logistic regression model, commonly used clinical-based scores, and a latest high-performance ML-based XGBoost model. The study revealed that the XGBoost model outperformed other two traditional models, achieving an AUROC of 0.929 in predicting the prognosis changes of stroke patients followed for 3 months. In addition, the XGBoost model maintained remarkably high precision even when using only selected 20 most relevant clinical features compared to full clinical datasets used in the study. These selected features closely correlated with significant changes in clinical outcomes for stroke patients and showed to be effective for predicting prognosis changes after discharge, allowing physicians to make optimal decisions regarding their patients’ recovery. Graphical Abstract

Development of a high-throughput kinase activity platform using nanoLC-MS/MS with DIA approach for studying the anti-cancer mechanism of Taxol in ovarian cancer - Chia-Hsin Lee; Yu-Ching Liu; Chao-Jung Chen (Analytica Chimica Acta, 2024)

CCL4 contributes to aging related angiogenic insufficiency through activating oxidative stress and endothelial inflammation - Ting-Ting Chang; Liang-Yu Lin; Ching Chen; Jaw-Wen Chen (Angiogenesis, 2024)
Aging is a natural process associated with chronic inflammation in the development of vascular dysfunction. We hypothesized that chemokine C-C motif ligands 4 (CCL4) might play a vital role in aging-related vascular dysfunction. Circulating CCL4 was up-regulated in elderly subjects and in aged animals. CCL4 inhibition reduced generation of reactive oxygen species (ROS), attenuated inflammation, and restored cell functions in endothelial progenitor cells from elderly subjects and in aged human aortic endothelial cells. CCL4 promoted cell aging, with impaired cell functioning, by activating ROS production and inflammation. CCL4 knockout mice and therapeutic administration of anti-CCL4 neutralizing antibodies exhibited vascular and dermal anti-aging effects, with improved wound healing, via the down-regulation of inflammatory proteins and the activation of angiogenic proteins. Altogether, our findings suggested that CCL4 may contribute to aging-related vascular dysfunction via activating oxidative stress and endothelial inflammation. CCL4 may be a potential therapeutic target for vascular protections during aging.

Efficiency of PGK1 proteins delivered to the brain via a liposomal system through intranasal route administration for the treatment of spinocerebellar ataxia type 3 - Yu-Shuan Chen; Zhen-Xiang Hong; Yi-Tung Lin; En-CI Tsao; Pei-Yu Chen; Ching-Ann Liu; Horng-Jyh Harn; Tzyy-Wen Chiou; Shinn-Zong Lin (Drug Delivery and Translational Research, 2024)

Assessment of PM2.5-associated mortality burden among the elderly: Insights into demographic, socio-economic, and geographic factors - Ayushi Sharma; Hsi-yu Hsiao; Jia-Yi Liu; Shih-Chun Candice Lung; Huey-Jen Su; Ching-Fen Shen; Nai-Tzu Chen; Pei-Chih Wu; Cheng-Yu Lin; Sheng-Fu Liang; Tain-Junn Cheng; Ta-Chien Chan; et al. (Air Quality, Atmosphere & Health, 2024)

Isolation of 24-homoscalarane sesterterpenoids from a sponge of the genus Lendenfeldia - Li-Guo Zheng; You-Yan Chen; Chia-Ching Liaw; Yu-Chi Lin; Su-Ying Chien; Yi-Hao Lo; Yu-Chi Tsai; Hao-Chun Hu; You-Ying Chen; Tsong-Long Hwang; Tzu-Ming Ou; Ping-Jyun Sung (Phytochemistry Letters, 2024)

Examining arterial pulsation to identify and risk-stratify heart failure subjects with deep neural network - Chieh-Chun Huang; Shih-Hsien Sung; Wei-Ting Wang; Yin-Yuan Su; Chi-Jung Huang; Tzu-Yu Chu; Shao-Yuan Chuang; Chern-En Chiang; Chen-Huan Chen; Chen-Ching Lin; Hao-Min Cheng (Physical and Engineering Sciences in Medicine, 2024)
Hemodynamic parameters derived from pulse wave analysis have been shown to predict long-term outcomes in patients with heart failure (HF). Here we aimed to develop a deep-learning based algorithm that incorporates pressure waveforms for the identification and risk stratification of patients with HF. The first study, with a case–control study design to address data imbalance issue, included 431 subjects with HF exhibiting typical symptoms and 1545 control participants with no history of HF (non-HF). Carotid pressure waveforms were obtained from all the participants using applanation tonometry. The HF score, representing the probability of HF, was derived from a one-dimensional deep neural network (DNN) model trained with characteristics of the normalized carotid pressure waveform. In the second study of HF patients, we constructed a Cox regression model with 83 candidate clinical variables along with the HF score to predict the risk of all-cause mortality along with rehospitalization. To identify subjects using the HF score, the sensitivity, specificity, accuracy, F1 score, and area under receiver operating characteristic curve were 0.867, 0.851, 0.874, 0.878, and 0.93, respectively, from the hold-out cross-validation of the DNN, which was better than other machine learning models, including logistic regression, support vector machine, and random forest. With a median follow-up of 5.8 years, the multivariable Cox model using the HF score and other clinical variables outperformed the other HF risk prediction models with concordance index of 0.71, in which only the HF score and five clinical variables were independent significant predictors (p < 0.05), including age, history of percutaneous coronary intervention, concentration of sodium in the emergency room, N -terminal pro-brain natriuretic peptide, and hemoglobin. Our study demonstrated the diagnostic and prognostic utility of arterial waveforms in subjects with HF using a DNN model. Pulse wave contains valuable information that can benefit the clinical care of patients with HF.

The effects of Elgucare in a rat model of intervertebral disc degeneration - Ting-Kuo Chang; Yueh-Ching Liu; Tzu-Yun Chien; Yu-Ting Chen; Ching-Chen Chen (Advances in Traditional Medicine, 2024)
As an avascular tissue, the intervertebral disc (IVD) faces difficulties in obtaining nutrients and is prone to accumulating metabolic waste. The ensuing IVD degeneration (IVDD) causes symptoms such as low back pain. Traditional Chinese medicine has a millennia-long history of treating IVDD, with the advantages of safety and few adverse effects. Based on prior pharmacological research, the Chinese herbal formula Elgucare is abundant in the nutrients required by the IVD and can improve blood circulation, accelerating the removal of metabolic waste from the IVD. This study used a 23 G needle to surgically induce IVDD in a rat model. Thirty rats were randomly assigned to five groups: one that underwent sham surgery (Sham), one with IVDD that was not fed Elgucare (EGC-0), and three with IVDD that were fed Elgucare at different concentrations for six weeks (EGC-L, EGC-M, and EGC-H). Study parameters, including total body weight, plantar sensitivity to pain, gait analysis, IVD thickness, and IVD morphology, were used to assess the effects of Elgucare on IVDs. Our results showed that administering Elgucare to rats effectively reduced plantar tingling and improved swing speed during gait analysis. Elgucare also accelerated increases in IVD thickness and increased the proportion of IVD that returned to normal cellularity. The possible benefits of Elgucare include alleviating pain, improving mobility, and accelerating IVD repair, indicating its potential for use in IVD therapy.

Effects of occupational exposure to metal fume PM2.5 on lung function and biomarkers among shipyard workers: a 3-year prospective cohort study - Huan Minh Tran; Ching-Huang Lai; Wei-Liang Chen; Chung Ching Wang; Che-Wei Liang; Chi-Yu Chien; Chih-Hong Pan; Kai-Jen Chuang; Hsiao-Chi Chuang (International Archives of Occupational and Environmental Health, 2024)
Objective This study investigates the associations of α1-antitrypsin, inter-α-trypsin inhibitor heavy chain (ITIH4), and 8-isoprostane with lung function in shipyard workers exposed to occupational metal fume fine particulate matter (PM 2.5 ), which is known to be associated with adverse respiratory outcomes. Methods A 3-year follow-up study was conducted on 180 shipyard workers with 262 measurements. Personal exposure to welding fume PM 2.5 was collected for an 8-h working day. Pre-exposure, post-exposure, and delta (∆) levels of α1-antitrypsin, ITIH4, and 8-isoprostane were determined in urine using enzyme-linked immunosorbent assays. Post-exposure urinary metals were sampled at the beginning of the next working day and analyzed by inductively coupled plasma-mass spectrometry. Lung function measurements were also conducted the next working day for post-exposure. Results An IQR increase in PM 2.5 was associated with decreases of 2.157% in FEV 1 , 2.806% in PEF, 4.328% in FEF 25% , 5.047% in FEF 50% , and 7.205% in FEF 75% . An IQR increase in PM 2.5 led to increases of 42.155 µg/g in ∆α1-antitrypsin and 16.273 µg/g in ∆ITIH4. Notably, IQR increases in various urinary metals were associated with increases in specific biomarkers, such as post-urinary α1-antitrypsin and ITIH4. Moreover, increases in ∆ α1-antitrypsin and ∆ITIH4 were associated with decreases in FEV 1 /FVC by 0.008% and 0.020%, respectively, and an increase in ∆8-isoprostane resulted in a 1.538% decline in FVC. Conclusion Our study suggests that urinary α1-antitrypsin and ITIH4 could indicate early lung function decline in shipyard workers exposed to metal fume PM 2.5 , underscoring the need for better safety and health monitoring to reduce respiratory risks. Graphical abstract

The Association of Bisphenol A and Parabens Exposure and Oxidative Stress in Attention-Deficit/Hyperactivity Disorder in Children and Adolescents - Boopathi Subramani; Chia-Huang Chang; Ting-Yu Fang; Ching-Jung Yu; Jung-Chieh Du; Hsien-Chih Chiou; Jia-Woei Hou; Winnie Yang; Hsin-Chang Chen; Ying-Sheue Chen; Betau Hwang; Mei-Lien Chen (Exposure and Health, 2024)

Photo-protection and photo-inhibition during light induction in Barbula indica and Conocephalum conicum under different light gradients - Chung-I. Chen; Kuan-Hung Lin; Meng-Yuan Huang; Kuei-Yu Yao; Chau-Ching Huang; Tzu-Chao Lin; En-Liang Chu; Jia-Dong Yang; Ching-Wen Wang (Photosynthesis Research, 2024)

Isolation and characterization of the novel phage BP14 for lysing Vibrio parahaemolyticus and reducing virulence proteins - Te-Ken Hsu; Hui-Yu Shih; Hui-Ju Huang; Jeff Chia-Kai Hsu; Han-Ching Wang; Yi-Yin Chen; Li-Li Chen (Aquaculture, 2024)

Exploring the multifaceted impact of lanthanides on physiological pathways in human breast cancer cells - Yi-Ming Huang; Tsu-Yu Hsu; Ching-Yu Liu; Yu-Chen Hsieh; Kuan-Yun Lai; Ya-Wen Yang; Kai-Yin Lo (Toxicology, 2024)

Exposure estimates of PM2.5 using the land-use regression with machine learning and microenvironmental exposure models for elders: Validation and comparison - Chin-Yu Hsu; Wei-Ting Hsu; Ching-Yi Mou; Pei-Yi Wong; Chih-Da Wu; Yu-Cheng Chen (Atmospheric Environment, 2024)

Effect of stress on the rehabilitation performance of rats with repetitive mild fluid percussion-induced traumatic brain injuries - Yu-Lin Wang; Chi-Chun Chen; Ching-Ping Chang (Cognitive Neurodynamics, 2024)

Semi-analytical models for two-dimensional multispecies transport of sequentially degradation products influenced by rate-limited sorption subject to arbitrary time-dependent inlet boundary conditions - Thu-Uyen Nguyen; Yu-Chieh Ho; Heejun Suk; Ching-Ping Liang; Zhong-Yi Liao; Jui-Sheng Chen (Advances in Water Resources, 2024)

Green cost performance measure of China’s thermal power industry: evidence from Chinese 30 provinces - Xiang Chen; Jiayu Zhang; Chih-Yu Yang; Ching-Cheng Lu; Jun Wang (Environment, Development and Sustainability, 2024)

A longitudinal study on the change in sleep across three waves of the COVID-19 outbreaks in Hong Kong - Denise Shuk Ting Cheung; Branda Yee-Man Yu; Simon Ching Lam; Doris Yin Ping Leung; Ka-Fai Chung; Fiona Yan-Yee Ho; Shu-Cheng Chen; Wing-Fai Yeung (Sleep and Biological Rhythms, 2024)

Evaluating the toxic mechanism of 1,2-diacetylbenzene in neural cells/tissues: The favorable impact of silibinin - Li-Yu Fay; Jun-Yi Chien; Ching-Feng Weng; Huai-Sheng Kuo; Dann-Ying Liou; Wei-Hao Weng; Chi-Hung Lin; Ya-Tzu Chen; Wen-Hung Huang; Wen-Cheng Huang; May-Jywan Tsai; Henrich Cheng (NeuroToxicology, 2023)

A crosslinked waterborne poly(vinyl acetate) for greenhouse gas fixation with improved elastomeric properties, shape-memory ability, and recyclability - Yen-Chuan Chen; Ying-Chi Huang; Yi-Hua Huang; Ying-Feng Lin; Ho-Ching Huang; Ru-Jong Jeng; Yu-Wei Cheng; Chien-Hsin Wu (Journal of Environmental Chemical Engineering, 2023)

Tandem surface engineering of graphene quantum dot-assisted fluorinated NiFe Prussian blue analogue for electrocatalytic oxygen evolution reaction - Angelina Melanita Tarigan; Sofiannisa Aulia; Mia Rinawati; Ling-Yu Chang; Yao-Sheng Cheng; Ching-Cheng Chang; Wei-Hsiang Huang; Jeng-Lung Chen; Heru Setyawan; Min-Hsin Yeh (Chemical Engineering Journal, 2023)

Uncovering molecular mechanisms involved in microbial volatile compounds-induced stomatal closure in Arabidopsis thaliana - Tu-Trinh Thi Truong; Chi-Chou Chiu; Jing-Yu Chen; Pei-Yu Su; Tri-Phuong Nguyen; Ngoc-Nam Trinh; Tetsuro Mimura; Ruey-Hua Lee; Ching-Han Chang; Hao-Jen Huang (Plant Molecular Biology, 2023)

Interaction between driftwood deposition patterns and debris flow fan development - Yen-Yu Chiu; Jia-Yen Wu; Hung-En Chen; Ching-Ying Tsou; Su-Chin Chen (Landslides, 2023)

First principal observation documenting the three-dimensional uptake of cadmium and spatial distribution of cadmium hydroxyapatite mineral in bone char - Partha Pratim Biswas; Jagat Rathod; Ching-Yu Chiang; Biqing Liang; Chun-Chieh Wang; Yao-Chang Lee; Yu-Chun Chuang; Prakash C. Loni; Wei-Hsin Chen; Shan-Li Wang (Chemosphere, 2023)

The biocompatibility and hemostatic efficacy of silk fibroin nanofibrils fabricated by Shear-Induced phase separation process - Po-Wen Lu; Yu-Tzu Wu; Liang-Yu Chang; Tzu-Wei Lu; Chonlachat Jaihao; Ching-Shuan Huang; Mo-Fei Murphy Chuang; Chunche Lin; Innie Chen; Agnese Brangule; Aleksej Zarkov; Aivaras Kareiva; et al. (Chemical Engineering Journal, 2023)

Hybridize magnesium-iron layered double hydroxide with biopolymers to develop multiple pathways for phosphate sorption and release: A potential slow release phosphorus fertilizer - Wen-Hui Li; Liang-Ching Hsu; Yu-Min Tzou; Yi-Chun Chen; Heng Yi Teah; Yu-Yu Kung; Han-Yu Chen; Yu-Ting Liu (Chemical Engineering Journal, 2023)

Severity of Liver Cirrhosis Evaluated by Digital Subtraction Angiography Using Quantitative Color-Coding Analysis Before Transarterial Embolization - Lung-Hui Giiang; Chang-Hsien Liu; Chih-Yung Yu; Te-Pao Lin; Hsiang-Cheng Chen; Chun-Jung Juan; Yu-Ching Chou (Journal of Medical and Biological Engineering, 2023)

Capture of colloidal fine suspended particle by aquatic vegetation under rainfall - Congrong Yu; Xiuhui Ye; Ying Li; Ching-Sheng Huang; Zhongbo Yu; Gang Chen; Xiaoxiao Hao (Science of The Total Environment, 2023)

Effect of indoor air quality on the association of long-term exposure to low-level air pollutants with cognition in older adults - Yen-Ching Chen; Pei-Iun Hsieh; Jia-Kun Chen; Emily Kuo; Hwa-Lung Yu; Jeng-Min Chiou; Jen-Hau Chen (Environmental Research, 2023)

Cleanup of Cr(VI)-polluted groundwater using immobilized bacterial consortia via bioreduction mechanisms - Wei-Han Lin; Chih-Ching Chien; Jiun-Hau Ou; Ying-Liang Yu; Ssu-Ching Chen; Chih-Ming Kao (Journal of Environmental Management, 2023)

Regulating energy gap in Ir-based ionic complexes to generate near-infrared emissions: Application in solid-state light-emitting electrochemical cells - Yan-Ding Lin; Pei-Wan Hsiao; Wun-Yu Chen; Sih-Yu Wu; Wei-Min Zhang; Chin-Wei Lu; Hai-Ching Su (Chemical Engineering Journal, 2023)

Rat Hair Metabolomics Analysis Reveals Perturbations of Unsaturated Fatty Acid Biosynthesis, Phenylalanine, and Arachidonic Acid Metabolism Pathways Are Associated with Amyloid-β-Induced Cognitive Deficits - Tian-Hoe Tan; Shih-Wen Li; Chih-Wei Chang; Yuan-Chih Chen; Yu-Hsuan Liu; Jui-Ti Ma; Ching-Ping Chang; Pao-Chi Liao (Molecular Neurobiology, 2023)
Hair is a noninvasive valuable biospecimen for the long-term assessment of endogenous metabolic disturbance. Whether the hair is suitable for identifying biomarkers of the Alzheimer’s disease (AD) process remains unknown. We aim to investigate the metabolism changes in hair after β-amyloid (Aβ 1-42 ) exposure in rats using ultra-high-performance liquid chromatography-high-resolution mass spectrometry–based untargeted and targeted methods. Thirty-five days after Aβ 1-42 induction, rats displayed significant cognitive deficits, and forty metabolites were changed, of which twenty belonged to three perturbed pathways: (1) phenylalanine metabolism and phenylalanine, tyrosine, and tryptophan biosynthesis— l -phenylalanine, phenylpyruvate, ortho-hydroxyphenylacetic acid, and phenyllactic acid are up-regulated; (2) arachidonic acid (ARA) metabolism—leukotriene B4 (LTB4), arachidonyl carnitine, and 5(S)-HPETE are upregulation, but ARA, 14,15-DiHETrE, 5(S)-HETE, and PGB2 are opposite; and (3) unsaturated fatty acid biosynthesis— eicosapentaenoic acid (EPA), docosahexaenoic acid (DHA), FA 18:3 + 1O, and FA 18:3 + 2O are downregulated. Linoleic acid metabolism belonging to the biosynthesis of unsaturated fatty acid includes the upregulation of 8-hydroxy-9,10-epoxystearic acid, 13-oxoODE, and FA 18:2 + 4O, and downregulation of 9(S)-HPODE and dihomo-γ-linolenic acid. In addition, cortisone and dehydroepiandrosterone belonging to steroid hormone biosynthesis are upregulated. These three perturbed metabolic pathways also correlate with cognitive impairment after Aβ 1-42 stimulation. Furthermore, ARA, DHA, EPA, l -phenylalanine, and cortisone have been previously implicated in the cerebrospinal fluid of AD patients and show a similar changing trend in Aβ 1-42 rats’ hair. These data suggest hair can be a useful biospecimen that well reflects the expression of non-polar molecules under Aβ 1-42 stimulation, and the five metabolites have the potential to serve as novel AD biomarkers.

New ent -kaurene and germacrene derivatives from Mesona procumbens Hemseley and their biological activity - Jerome G. Ganzon; Chia-Ching Liaw; Yu-Chi Lin; Zhi-Hu Lin; Chang-Hung Wang; Che-Yi Chen; Kuo-Hsiang Chuang; Yao-Haur Kuo (Natural Product Research, 2023)

Estimating arsenic biotransfer factors from feed to chicken: a viable approach to animal feed risk assessment - Ching-Chi Hung; Hsin-Tang Lin; Ching-Yi Chen; Kuan-Yi Chen; Tsung-Yu Lee; Chow-Feng Chiang (Food Additives & Contaminants: Part A, 2023)

Corrigendum to: “Exposure to polystyrene microplastics impairs hippocampus-dependent learning and memory in mice” J. Hazard. Mater. 430 (2022) 128431 - Chiang-Wen Lee; Lee-Fen Hsu; I.-Lin Wu; Yung-Li Wang; Wei-Chen Chen; Yan-Jun Liu; Lu-Tang Yang; Chong-Lun Tan; Yueh-Hsia Luo; Chia-Ching Wang; Hui-Wen Chiu; Thomas Chung-Kuang Yang; et al. (Journal of Hazardous Materials, 2023)

Phylogenetic divergence associated with climate oscillations and topology illustrates the dispersal history of Formosan sambar deer (Rusa unicolor swinhoii) in Taiwan - Kuan-Yi Li; Chen Hsiao; Shih-Ching Yen; Chien-Yi Hung; You-Zhu Lin; Sheng-Wun Jheng; Pei-Ju Yu; Mei-Hsiu Hwang; Guo-Jing Weng; Ku-Lin Chen; Shu-Fen Lin; Shih-Wei Chang; et al. (Mammal Research, 2023)
The island of Taiwan represents an ideal context for studying the effects of climatic oscillations and topographic variation on large herbivores due to its varied tropical to sub-tropical climate zones at different elevational ranges. We explored the phylogenetics of Formosan sambar deer ( Rusa unicolor swinhoii ) using the control region of the mitochondrial genome. We detected 18 haplotypes among 454 sequences across the island and grouped them into six regions based on SAMOVA, with 68.78% variance among regions. A Bayesian phylogenetic dendrogram revealed two spatially segregated genetic clades. Neutrality tests and Bayesian skyline plots uncovered different demographic expansion histories for the two clades. We further tested divergence times and chronology to propose potential phylogenetic scenarios, which were examined using approximate Bayesian computation. Finally, we present a credible hypothesis for a glacial refugium in the northern part of the Central Mountain Range. Subsequent secondary contact between the two clades during interglacial periods has led to the extant genetic structure of Formosan sambar deer.

Effect of polysaccharide derived from dehulled adlay on regulating gut microbiota and inhibiting Clostridioides difficile in an in vitro colonic fermentation model - Bao-Hong Lee; Shih-Ching Huang; Chih-Yao Hou; You-Zuo Chen; Yu-Hsin Chen; Sulfath Hakkim Hazeena; Wei-Hsuan Hsu (Food Chemistry, 2023)

Long-term DEHP/MEHP exposure promotes colorectal cancer stemness associated with glycosylation alterations - Pei-Chun Shih; Hsin-Pao Chen; Ching-Cheng Hsu; Chung-Hsien Lin; Chou-Yuan Ko; Chao-Wen Hsueh; Cheng-Yi Huang; Tian-Huei Chu; Cheng-Chun Wu; Yu-Cheng Ho; Ngoc Uyen Nhi Nguyen; Shih-Chung Huang; et al. (Environmental Pollution, 2023)

Early-onset caloric restriction alleviates ageing-associated steatohepatitis in male mice via restoring mitochondrial homeostasis - Chun-Hsien Chiang; Sin-Jin Li; Yu-Han Lin; Pei-Yu Wang; Pu-Sheng Hsu; Shau-Ping Lin; Ting-Chia Chiang; Ching-Yi Chen (Biogerontology, 2023)

Building high-capacity mesoporous adsorbents for fluoride removal through increased surface oxygen anions using organogel-assisted synthesis - Wei-Fan Kuan; Fang-Yu Chang; Jhih-Jing Chang; Hsuan-Chih Kuo; Chia-Hsun Hsieh; Jenn Fang Su; Ching-Lung Chen (Journal of Cleaner Production, 2023)

Homogenization of spatially variable hydraulic conductivity in the presence of a geotechnical structure - Jianye Ching; Zhi-Yu Chen; Kok-Kwang Phoon (Computers and Geotechnics, 2023)

Removal and concurrent reduction of Cr(VI) by thermoacidophilic Cyanidiales: a novel extreme biomaterial enlightened for acidic and neutral conditions - Yen-Lin Cho; Yu-Min Tzou; Chun-Chieh Wang; Yao-Chang Lee; Liang-Ching Hsu; Shao-Lun Liu; Afifah Assakinah; Yu-Hsien Chen; Nhu Anh Thi Than; Yu-Ting Liu; Jörg Rinklebe (Journal of Hazardous Materials, 2023)

Bouguer gravity anomalies and the three-dimensional density structure of a thick mudstone area: A case study of southwestern Taiwan - Yu-Tsung Lo; Kuo-En Ching; Horng-Yuan Yen; Song-Chuen Chen (Tectonophysics, 2023)

Multi-objective operation optimization of spent coffee ground torrefaction for carbon–neutral biochar production - Wei-Hsin Chen; Kuan-Ting Lee; Kuan-Yu Ho; Alvin B. Culaba; Veeramuthu Ashokkumar; Ching Joon Juan (Bioresource Technology, 2023)

Bioremediation potential of cadmium by recombinant Escherichia coli surface expressing metallothionein MTT5 from Tetrahymena thermophila - Che-Wei Lu; Hsin-Cheng Ho; Chao-Ling Yao; Tsung-Yu Tseng; Chih-Ming Kao; Ssu-Ching Chen (Chemosphere, 2023)

CO2 dynamics in a small and old subtropical reservoir in East Asia: Environmental controls driving seasonal and spatial variability - Chun Ngai Chan; Matthew J. Bogard; Fong Ching Ma; Yu Ching Ip; Boyi Liu; Shuai Chen; Lishan Ran (Science of The Total Environment, 2023)

Identification of serum metabolic signatures of environmental-leveled phthalate in the Taiwanese child population using NMR-based metabolomics - Sheng-Han Lee; Zhi-Yi Du; Wei-Chen Tseng; Wan-Yu Lin; Mei-Huei Chen; Ching-Chun Lin; Hao-Jan Liang; Hui-Ju Wen; Yue-Leon Guo; Pau-Chung Chen; Ching-Yu Lin (Environmental Pollution, 2023)

13.2% EQE near-infrared TADF OLED with emission peak at 761 nm - Jing-Wen Tai; Yukun Tang; Kai Zhang; Chen-Zong Yang; Ze-Hui Pan; Yu-Ching Lin; Yu-Wei Shih; Chia-Hsun Chen; Tien-Lung Chiu; Jiun-Haw Lee; Chuan-Kui Wang; Chung-Chih Wu; et al. (Chemical Engineering Journal, 2023)

Doping engineering of carrier transporting layers for ambient-air-stable lead-free rudorffite solar cells prepared by thermal-assisted doctor blade coating - Kai-Chi Hsiao; Yen-Fu Yu; Ching-Mei Ho; Meng-Huan Jao; Yu-Hsiang Chang; Shih-Hsuan Chen; Yin-Hsuan Chang; Wei-Fang Su; Kun-Mu Lee; Ming-Chung Wu (Chemical Engineering Journal, 2023)

The involvement of AtMKK1 and AtMKK3 in plant-deleterious microbial volatile compounds-induced defense responses - Ching-Han Chang; Wu-Guei Wang; Pei-Yu Su; Yu-Shuo Chen; Tri-Phuong Nguyen; Jian Xu; Masaru Ohme-Takagi; Tetsuro Mimura; Ping-Fu Hou; Hao-Jen Huang (Plant Molecular Biology, 2023)

Durations of virtual exposure to built and natural landscapes impact self-reported stress recovery: evidence from three countries - Pongsakorn Suppakittpaisarn; Chia-Ching Wu; Yu-Hsin Tung; Yu-chen Yeh; Chulalux Wanitchayapaisit; Matthew H. E. M. Browning; Chun-Yen Chang; William C. Sullivan (Landscape and Ecological Engineering, 2023)

Development of the dried blood spot preparation protocol for comprehensive evaluation of the hematocrit effect - Chih-Ning Cheng; Yu-Fong Peng; Ju-Yu Chen; Guan-Yuan Chen; Te-I Weng; Ching-Hua Kuo (Analytica Chimica Acta, 2023)

ZAKβ Alleviates Oxidized Low-density Lipoprotein (ox-LDL)-Induced Apoptosis and B-type Natriuretic Peptide (BNP) Upregulation in Cardiomyoblast - Yueh-Min Lin; Jiro Hasegawa Situmorang; Jia-Zun Guan; Dennis Jine-Yuan Hsieh; Jaw-Ji Yang; Michael Yu-Chih Chen; Ching-Hui Loh; Chia-Hua Kuo; Shang-Yeh Lu; Ying-Ming Liou; Chih-Yang Huang (Cell Biochemistry and Biophysics, 2022)

Streptococcus vulneris sp. nov., isolated from wound of patient with diabetic foot ulcer (DFU) - Jen-hao Chung; Li-Ting Wang; Yi-Sheng Chen; Yun-Shien Lee; Shih-Ting Lin; Yu-Chung Chang; Hui-Chung Wu; Yu-Jie Dai; Wei-Qi Liao; Fan-Ching Kao; Jui-hsiang Li (Archives of Microbiology, 2022)

Lactobacillus plantarum PS128 Promotes Intestinal Motility, Mucin Production, and Serotonin Signaling in Mice - Chih-Ming Chen; Chien-Chen Wu; Chin-Lin Huang; Min-Yu Chang; Shih-Hsuan Cheng; Ching-Ting Lin; Ying-Chieh Tsai (Probiotics and Antimicrobial Proteins, 2022)
Lactobacillus plantarum PS128 has been reported as a psychobiotic to improve mental health through the gut–brain axis in experimental animal models. To explore its mechanism of action in the gut, this study aimed to analyze the effects of L. plantarum PS128 ingestion on naïve and loperamide (Lop)-induced constipation mice. We found that, in the two mouse models, the weight, number, and water content of feces in the L. plantarum PS128 group were higher than those in the vehicle control group. Histological observation revealed that L. plantarum PS128 increased the level of colonic mucins including the major mucin MUC2. In addition, the charcoal meal test showed that L. plantarum PS128 significantly increased the small intestine transit in naïve mice, but not in the Lop-treated mice. Since intestinal serotonin has been found to modulate motility, we further analyzed the expression of genes related to serotonin signal transduction in the small intestine of naïve mice. The results showed that L. plantarum PS128 significantly altered the expression levels of Tph1 , Chga , Slc6a4 , and Htr4 , but did not affect the expression levels of Tph2 , Htr3a , and Maoa . Furthermore, immunohistochemistry revealed that L. plantarum PS128 significantly increased the number of serotonin-containing intestinal cells in mice. Taken together, our results suggest that L. plantarum PS128 could promote intestinal motility, mucin production, and serotonin signal transduction, leading to a laxative effect in mice.

Geographic distance, sedimentation, and substrate shape cryptic crustose coralline algal assemblages in the world’s largest subtropical intertidal algal reef - Shing Hei Zhan; Ling Chen; Chen‐Pan Liao; Wun‐Ruei Chang; Cheng‐Chin Li; Guang‐You Tang; Ching‐Yu Liou; Wei‐Lung Wang; Shih‐Wei Wang; Shao‐Lun Liu (Molecular Ecology, 2022)
Algal reefs, concreted by crustose coralline algae (CCA), are the main biotic reefs in temperate waters but rare in the subtropics and tropics. The world's largest known intertidal algal reef in the subtropics is the Taoyuan Algal Reef (TAR) located in the northwestern coast of Taiwan. The biodiversity and ecology of the TAR are scarcely explored, and now the reef is imperiled by industrialization. Here, we document cryptic species of CCA in Taiwan, particularly the TAR, by sequencing the psb A genes of over 1800 specimens collected across Taiwan. We also examine the ecological background of the TAR by surveying its benthic composition and measuring its environmental parameters. Our data reveal that the TAR harbours a high diversity of cryptic CCA species (27 molecular operational taxonomic units, or mOTUs), many of which are potentially new to science (18 mOTUs) and/or endemic to the TAR (9 mOTUs). Comparing the CCA species inventory of the TAR with the rest of Taiwan shows that the TAR represents a unique hotspot of CCA taxa in the waters of Taiwan. Our analyses show that variation in the CCA assemblages in the TAR is associated with geographic distance, sedimentation, and substrate type (for example, reef vs. hermit crab shell), suggesting that dispersal limitation and contemporary environmental selection shape the CCA assemblages in the TAR. The data from this study can inform the monitoring of human impacts on the health of the TAR and contribute to our understanding of the ecological processes underlying algal reef development.

Interleukin-6 transiently promotes proliferation of osteoclast precursors and stimulates the production of inflammatory mediators - Peng-Yuan Chang; Hung-Kang Wu; Yu-Hsu Chen; Yu-Pao Hsu; Ming-Te Cheng; Ching-Hsiao Yu; Shau-Kwaun Chen (Molecular Biology Reports, 2022)

Reoxygenation of the Hypoxia in the East China Sea: A Ventilation Opening for Marine Life - Chung-Chi Chen; Dong S. Ko; Gwo-Ching Gong; Chun-Chi Lien; Wen-Chen Chou; Hung-Jen Lee; Fuh-Kwo Shiah; Yu-Sin Wita Huang (Frontiers in Marine Science, 2022)
Hypoxia and upwelling co-occur in the summer, and well-mixed water typically reaches the subsurface in the East China Sea (ECS), especially off the Changjiang River estuary. The impact of upwelling on hypoxia and, therefore, on the ecosystem in the ECS is not known. This study demonstrates both positive and negative effects of upwelling on hypoxia and its impact on the ecosystem. With upwelling, the spatial extent of hypoxic water increases with a lower pH but waters with high regenerated nutrients and fugacity of CO 2 ( f CO 2 ), which are normally confined to the near-bottom, are found just up to 5–10 m below the surface. This upwelled high nutrient water can enhance phytoplankton growth in this region. On one occasion in August 2014, upwelling reached to the surface and lasted for 3 weeks, with the area of coverage ranging from 326.8 to 24,368.0 km 2 . During this event, the water was mixed thoroughly throughout the water column, with high concentrations of nutrients, chlorophyll a , and slightly undersaturated dissolved oxygen but saturated f CO 2 , alongside a normal pH. This event may have served as an important pathway from the ocean to the atmosphere for the regenerated CO 2 . It also provided a productive and suitable environment for marine life and ventilation to alleviate low-oxygen stress in this hypoxic but upwelling region in the ECS.

A Unique Diel Pattern in Carbonate Chemistry in the Seagrass Meadows of Dongsha Island: The Enhancement of Metabolic Carbonate Dissolution in a Semienclosed Lagoon - Wen-Chen Chou; Lan-Feng Fan; Chang-Chang Yang; Ying-Hsuan Chen; Chin-Chang Hung; Wei-Jen Huang; Yung-Yen Shih; Keryea Soong; Hsiao-Chun Tseng; Gwo-Ching Gong; Hung-Yu Chen; Cheng-Kuan Su (Frontiers in Marine Science, 2021)
In contrast to other seagrass meadows where seawater carbonate chemistry generally shows strong diel variations with higher pH but lower partial pressure of CO 2 ( p CO 2 ) during the daytime and lower pH but higher p CO 2 during nighttime due to the alternation in photosynthesis and respiration, the seagrass meadows of the inner lagoon (IL) on Dongsha Island had a unique diel pattern with extremely high pH and low p CO 2 across a diel cycle. We suggest that this distinct diel pattern in pH and p CO 2 could be associated with the enhancement of total alkalinity (TA) production coupled to carbonate sediment dissolution in a semienclosed lagoon. The confinement of the IL may hamper water exchange and seagrass detritus export to the adjacent open ocean, which may result in higher organic matter loading to the sediments, and longer residence time of the water in the IL, accompanied by microbial respiration (both aerobic and anaerobic) that may reduce carbonate saturation level to drive carbonate dissolution and thus TA elevation, thereby forming such a unique diel pattern in carbonate chemistry. This finding further highlights the importance of considering TA production through metabolic carbonate dissolution when evaluating the potential of coastal blue carbon ecosystems to buffer ocean acidification and to absorb atmospheric CO 2 , in particular in a semienclosed setting.

Effectiveness of palonosetron versus granisetron in preventing chemotherapy-induced nausea and vomiting: a systematic review and meta-analysis - Yu-Chen Hsu; Ching-Yao Chen; Ka-Wai Tam; Chin-Yu Hsu (European Journal of Clinical Pharmacology, 2021)

Streptococcus vaginalis sp. nov., a novel bacterial species isolated from vaginal swabs of a pregnant woman with diabetes - An-Shine Chao; Chiao-Yun Lin; Angel Chao; Yun-Shien Lee; Yu-Chung Chang; Hui-Chung Wu; Yu-Jie Dai; Wei-Qi Liao; Fan-Ching Kao; Yi-Sheng Chen (Archives of Microbiology, 2021)

Viable and Heat-Killed Probiotic Strains Improve Oral Immunity by Elevating the IgA Concentration in the Oral Mucosa - Wen-Yang Lin; Yi-Wei Kuo; Ching-Wei Chen; Yu-Fen Huang; Chen-Hung Hsu; Jia-Hung Lin; Cheng-Ruei Liu; Jui-Fen Chen; Ko-Chiang Hsia; Hsieh-Hsun Ho (Current Microbiology, 2021)
Oral-nasal mucosal immunity plays a crucial role in protecting the body against bacterial and viral invasion. Safe probiotic products have been used to enhance human immunity and oral health. In this study, we verified the beneficial effects of mixed viable probiotic tablets, consisting of Lactobacillus salivarius subsp. salicinius AP-32, Bifidobacterium animalis subsp. lactis CP-9, and Lactobacillus paracasei ET-66, and heat-killed probiotic tablets, consisting of L. salivarius subsp. salicinius AP-32 and L. paracasei ET-66, on oral immunity among 45 healthy participants. Participants were randomly divided into viable probiotic, heat-killed probiotic, and placebo groups. The administration of treatment lasted for 4 weeks. Saliva samples were collected at Weeks 0, 2, 4, and 6, and Lactobacillus , Bifidobacterium and Streptococcus mutans populations and IgA concentration were measured. IgA concentrations, levels of TGF-beta and IL-10 in PBMCs cells were quantified by ELISA method. Results showed that salivary IgA levels were significantly increased on administration of both the viable (119.30 ± 12.63%, *** P < 0.001) and heat-killed (116.78 ± 12.28%, *** P < 0.001) probiotics for 4 weeks. Among three probiotic strains, AP-32 would effectively increase the levels of TGF-beta and IL-10 in PBMCs. The oral pathogen Streptococcus mutans was significantly reduced on viable probiotic tablet administration (49.60 ± 31.01%, *** P < 0.001). The in vitro antibacterial test confirmed that viable probiotics effectively limited the survival rate of oral pathogens. Thus, this clinical pilot study demonstrated that oral probiotic tablets both in viable form or heat-killed form could exert beneficial effects on oral immunity via IL-10, TGB-beta mediated IgA secretion. The effective dosage of viable probiotic content in the oral tablet was 10 9 CFUs/g and the heat-killed oral tablet was 1 × 10 10 cells/g.

Anti-Inflammatory and anti-proliferative oleanane-type triterpene glycosides from the vine of Momordica cochinchinensis - Hung-Tse Huang; Yu-Chi Lin; Li-Jie Zhang; Chia-Ching Liaw; Hsin-Yen Chen; Ming-Tung Hsueh; Yao-Haur Kuo (Natural Product Research, 2021)

Phenylpropanoids and lignoids from the whole plant of Vaccinium emarginatum and their cytotoxicity against prostate cancer cells - Ping-Chen Tu; Yu-Chia Liang; Ming-Ching Kao; Louis Kuoping Chao; Mei-Hwei Tseng; Te-Ling Lu; Ping-Jyun Sung; Yueh-Hsiung Kuo (Natural Product Research, 2021)

Germination dynamics of allergenic fungal spores in respiratory mucus - Wan-Rou Lin; Szu-Yu Chen; Shih-Ching Hsiao; Pi-Han Wang (Aerobiologia, 2021)

Effect of selected sampling media, flow rate, and time on the sampling efficiency of a liquid impinger packed with glass beads for the collection of airborne viruses - Yen-Chi Chen; I-Jen Wang; Chih-Ching Cheng; Yu-Chiao Wu; Chun-Hsuan Bai; Kuo-Pin Yu (Aerobiologia, 2021)

Carbon monoxide-triggered health effects: the important role of the inflammasome and its possible crosstalk with autophagy and exosomes - Rong-Jane Chen; Yu-Hsuan Lee; Tzu-Hao Chen; Yu-Ying Chen; Ya-Ling Yeh; Ching-Ping Chang; Chien-Cheng Huang; How-Ran Guo; Ying-Jan Wang (Archives of Toxicology, 2021)

The Effect of Wave-Induced Current and Coastal Structure on Sediment Transport at the Zengwen River Mouth - Chun-Hung Pao; Jia-Lin Chen; Shih-Feng Su; Yu-Ching Huang; Wen-Hsin Huang; Chien-Hung Kuo (Journal of Marine Science and Engineering, 2021)
The mechanisms that control estuarine sediment transport are complicated due to the interaction between riverine flows, tidal currents, waves, and wave-driven currents. In the past decade, severe seabed erosion and shoreline retreat along the sandy coast of western Taiwan have raised concerns regarding the sustainability of coastal structures. In this study, ADCPs (Acoustic Doppler Current Profiler) and turbidity meters were deployed at the mouth of the Zengwen river to obtain the time series and the spatial distribution of flow velocities and turbidity during the base flow and flood conditions. A nearshore circulation model, SHORECIRC, has been adapted into a hybrid finite-difference/finite-volume, TVD (Total Variation Diminishing)-type scheme and coupled with the wave-spectrum model Simulating Waves Nearshore (SWAN). Conventional finite-difference schemes often produce unphysical oscillations when modeling coastal processes with abrupt bathymetric changes at river mouths. In contrast, the TVD-type finite volume scheme allows for robust treatment of discontinuities through the shock-capturing mechanism. The model reproduces water levels, waves, currents observed at the mouth of the Zengwen River reasonably well. The simulated residual sediment transport patterns demonstrate that the transport process at the river mouth is dominated by the interaction of the bathymetry and wave-induced currents when the riverine discharge was kept in reservoirs. The offshore residual transport causes erosion at the northern part of the river mouth, and the onshore residual transport causes accretion in the ebb tidal shoals around the center of the river mouth. The simulated morphological evolution displays significant changes on shallower deltas. The location with significant sea bed changes is consistent with the spot in which severe erosion occurred in recent years. Further analysis of morphological evolution is also discussed to identify the role of coastal structures, for example, the extension of the newly constructed groins near the river mouth.

Continental shelf morphology controlled by bottom currents, mud diapirism, and submarine slumping to the east of the Gaoping Canyon, off SW Taiwan - Yi-Ching Yeh; Chung-Lin Tsai; Shu-Kun Hsu; Hsiao-Shan Lin; Kuan-Ting Chen; Yen-Yu Cho; Chin-Wei Liang (Geo-Marine Letters, 2021)

Molecular survey of selected viral pathogens in wild leopard cats (Prionailurus bengalensis) in Taiwan with an emphasis on the spatial and temporal dynamics of carnivore protoparvovirus 1 - Chen-Chih Chen; Ai-Mei Chang; Wan-Jhen Chen; Po-Jen Chang; Yu-Ching Lai; Hsu-Hsun Lee (Archives of Virology, 2021)

Risk of incident gastroesophageal reflux disease (GERD) in patients with sleep disorders: a population-based cohort study - Yu-Hsien Cheng; Tao-Hsin Tung; Pei-En Chen; Ching-Yao Tsai (Sleep and Biological Rhythms, 2021)

A study of climate model responses of the western Pacific subtropical high to El Niño diversity - Mengyan Chen; Ting-Huai Chang; Ching-Teng Lee; Shih-Wei Fang; Jin-Yi Yu (Climate Dynamics, 2021)

Correction to: 4-Phenylbutyric acid protects against vasculitic peripheral neuropathy induced by ischaemia–reperfusion through attenuating endoplasmic reticulum stress - Cay‑Huyen Chen; Ping‑Chen Shih; Han‑Yu Lin; Po‑Kai Wang; Po‑Ting Pan; Ching‑Wei Chuang; Ming‑Chang Kao (Inflammopharmacology, 2020)

Overexpression of a multifunctional β-glucosidase gene from thermophilic archaeon Sulfolobus solfataricus in transgenic tobacco could facilitate glucose release and its use as a reporter - Chih-Hao Huang; Tzu-Ling Huang; Yu-Chang Liu; Ting-Chieh Chen; Shih-Ming Lin; Shyh-Yu Shaw; Ching-Chun Chang (Transgenic Research, 2020)

A new macrocyclic diterpenoid from Anisomeles indica - Chen-Liang Chao; Hui-Chi Huang; Hsiou-Yu Ding; Jenn-Haung Lai; Hang-Ching Lin; Wen-Liang Chang (Natural Product Research, 2020)

A field pilot-scale study on heavy metal-contaminated soil washing by using an environmentally friendly agent—poly-γ-glutamic acid (γ-PGA) - Yen-Ping Peng; Yu-Chen Chang; Ku-Fan Chen; Ching-Hsiang Wang (Environmental Science and Pollution Research, 2020)

New land use regression model to estimate atmospheric temperature and heat island intensity in Taiwan - Chin-Yu Hsu; Uen-Ching Ng; Chiao-Ying Chen; Yu-Cheng Chen; Mu-Jean Chen; Nai-Tzu Chen; Shih-Chun Candice Lung; Huey-Jen Su; Chih-Da Wu (Theoretical and Applied Climatology, 2020)

Targeting Inflammation, PHA-767491 Shows a Broad Spectrum in Protein Aggregation Diseases - Yu-Han Chung; Chia-Wei Lin; Hsin-Yu Huang; Shu-Ling Chen; Hei-Jen Huang; Ying-Chieh Sun; Guan-Chiun Lee; Guey-Jen Lee-Chen; Ya-Ching Chang; Hsiu Mei Hsieh-Li (Journal of Molecular Neuroscience, 2020)

Acute physiological responses to combined blood flow restriction and low-level laser - Yi-Ching Chen; Yu-Han Su; Yen-Ting Lin; Chien-Chun Huang; Ing-Shiou Hwang (European Journal of Applied Physiology, 2020)

Prior Antiplatelet Therapy, Excluding Phosphodiesterase Inhibitor Is Associated with Poor Outcome in Patients with Spontaneous Intracerebral Haemorrhage - Zhuo-Hao Liu; Chi-Hung Liu; Po-Hsun Tu; Ping K. Yip; Ching-Chang Chen; Yu-Chi Wang; Nan-Yu Chen; Yu-Sheng Lin (Translational Stroke Research, 2020)

Integrating Patient-Specific Electrocardiogram Signals and Image-Based Computational Fluid Dynamics Method to Analyze Coronary Blood Flow in Patients during Cardiac Arrhythmias - Szu-Hsien Chou; Kuan-Yu Lin; Zhen-Ye Chen; Chun-Jung Juan; Chien-Yi Ho; Tzu-Ching Shih (Journal of Medical and Biological Engineering, 2020)
Purpose The aim of this study was to use the computational fluid dynamics (CFD) method, patient-specific electrocardiogram (ECG) signals, and computed tomography three-dimensional image reconstruction technique to investigate the blood flow in coronary arteries during cardiac arrhythmia. Methods Two patients with premature ventricular contraction-type cardiac arrhythmia and one with atrial fibrillation-type cardiac arrhythmia were investigated. The inlet velocity of the coronary artery in simulation was applied with the measured velocity profile of the left ventricular outflow tract (LVOT) from the Doppler echocardiography. The measured patient central aortic blood pressure waveform was employed for the coronary artery outlet in simulation. The no-slip boundary condition was applied to the arterial wall. Results For the patient with irregular cardiac rhythms (Case I), the coronary blood flow rate under the shortened and lengthened cardiac rhythms were 0.66 and 0.96 mL/s, respectively. In Case II, the maximum velocity at the LVOT under a normal heartbeat was found to be 101 cm/s, whereas the average value was 73 cm/s. In Case III, the patient was also diagnosed with a congenital stenosis problem at the myocardial bridge (MCB) at the LAD. The measured blood flow rate at the MCB of the LAD for the three heartbeats in Case III was found to be 0.68, 1.08, and 1.14 mL/s. Conclusion The integration of patient-specific ECG signals and image-based CFD methods can clearly analyze hemodynamic information for patients during cardiac arrhythmia. The cardiac arrhythmia can reduce the blood flow in the coronary arteries.

Population Structure of the World Vegetable Center Mungbean Mini Core Collection and Genome-Wide Association Mapping of Loci Associated with Variation of Seed Coat Luster - Caleb Manamik Breria; Ching Hsiang Hsieh; Jo-Yi Yen; Ramakrishnan Nair; Chen-Yu Lin; Shu-Mei Huang; Thomas J. Noble; Roland Schafleitner (Tropical Plant Biology, 2020)

Pulse Oximetry Monitor Feasible for Early Screening of Obstructive Sleep Apnea (OSA) - Huei-Chen Lin; Chien-Ling Su; Jun-Hui Ong; kun-ling Tsai; Yu-Wen Chen; Cheng-Yu Lin; Ling-Ling Chiang; Ching-Hsia Hung (Journal of Medical and Biological Engineering, 2020)

Cold treatment for guava fruits infested with oriental fruit fly, Bactrocera dorsalis (Diptera: Tephritidae) - Kao W. Lin; Huey L. Lin; Ching C. Shiesh; Yu. L. Hsu; Chih. H. Lin; Su. C. Chen; Wen B. Yeh (Applied Entomology and Zoology, 2020)

Mutational signatures and mutagenic impacts associated with betel quid chewing in oral squamous cell carcinoma - Shih-Chi Su; Lun-Ching Chang; Chiao-Wen Lin; Mu-Kuan Chen; Chun-Ping Yu; Wen-Hung Chung; Shun-Fa Yang (Human Genetics, 2019)

In vitro activities of imipenem, vancomycin, and rifampicin against clinical Elizabethkingia species producing BlaB and GOB metallo-beta-lactamases - Tein-Yao Chang; Hsing-Yu Chen; Yu-Ching Chou; Yun-Hsiang Cheng; Jun-Ren Sun (European Journal of Clinical Microbiology & Infectious Diseases, 2019)

Indication of dynamic neurovascular coupling from inconsistency between EEG and fMRI indices across sleep–wake states - Changwei W. Wu; Pei-Jung Tsai; Sharon Chia-Ju Chen; Chia-Wei Li; Ai-Ling Hsu; Hong-Yi Wu; Yu-Ting Ko; Pai-Chuan Hung; Chun-Yen Chang; Ching-Po Lin; Timothy J. Lane; Chia-Yuen Chen (Sleep and Biological Rhythms, 2019)

Contrasting forms of competition set elevational range limits of species - Shih‐Fan Chan; Wei‐Kai Shih; An‐Yu Chang; Sheng‐Feng Shen; I‐Ching Chen (Ecology Letters, 2019)
How abiotic and biotic factors constrain distribution limits at the harsh and benign edges of species ranges is hotly debated, partly because macroecological experiments testing the proximate causes of distribution limits are scarce. It has long been recognized – at least since Darwin’s On the Origin of Species – that a harsh climate strengthens competition and thus sets species range limits. Using thorough field manipulations along a large elevation gradient, we show the mechanisms by which temperature determines competition type, resulting in a transition from interference to exploitative competition from the lower to the upper elevation limits in burying beetles ( Nicrophorus nepalensis ). This transition is an example of Darwin’s classic hypothesis that benign climates favor direct competition for highly accessible resources while harsh climates result in competition through resources of high rivalry. We propose that identifying the properties of these key resources will provide a more predictive framework to understand the interplay between biotic and abiotic factors in determining geographic range limits.

4-Phenylbutyric acid protects against vasculitic peripheral neuropathy induced by ischaemia–reperfusion through attenuating endoplasmic reticulum stress - Cay-Huyen Chen; Ping-Chen Shih; Han-Yu Lin; Po-Kai Wang; Po-Ting Pan; Ching-Wei Chuang; Ming-Chang Kao (Inflammopharmacology, 2019)

PARK14 (D331Y) PLA2G6 Causes Early-Onset Degeneration of Substantia Nigra Dopaminergic Neurons by Inducing Mitochondrial Dysfunction, ER Stress, Mitophagy Impairment and Transcriptional Dysregulation in a Knockin Mouse Model - Ching-Chi Chiu; Chin-Song Lu; Yi-Hsin Weng; Ying-Ling Chen; Ying-Zu Huang; Rou-Shayn Chen; Yi-Chuan Cheng; Yin-Cheng Huang; Yu-Chuan Liu; Szu-Chia Lai; Kun-Jun Lin; Yan-Wei Lin; et al. (Molecular Neurobiology, 2019)

Effects of Copper on Root Morphology, Cations Accumulation, and Oxidative Stress of Grapevine Seedlings - Kai-Wei Juang; Yu-Ching Lo; Tzu-Hsuan Chen; Bo-Ching Chen (Bulletin of Environmental Contamination and Toxicology, 2019)

Magnesium sulfate inhibits binding of lipopolysaccharide to THP-1 cells by reducing expression of cluster of differentiation 14 - Ya-Ying Chang; Tzu-Yu Lin; Ming-Chang Kao; Tsung-Ying Chen; Ching-Feng Cheng; Chih-Shung Wong; Chun-Jen Huang (Inflammopharmacology, 2019)

Mitochondrial Genetic Diversity of the Freshwater Snail Melanoides tuberculata - Yuh-Wen Chiu; Ye-Chen Gan; Po-Hsun Kuo; Kui-Ching Hsu; Mian-Shin Tan; Yu-Min Ju; Hung-Du Lin (Biochemical Genetics, 2019)

Adenosine Augmentation Evoked by an ENT1 Inhibitor Improves Memory Impairment and Neuronal Plasticity in the APP/PS1 Mouse Model of Alzheimer’s Disease - Chia-Chia Lee; Ching-Pang Chang; Chun-Jung Lin; Hsing-Lin Lai; Yu-Han Kao; Sin-Jhong Cheng; Hui-Mei Chen; Yu-Ping Liao; Emilie Faivre; Luc Buée; David Blum; Jim-Min Fang; et al. (Molecular Neurobiology, 2018)

Pre-treatment with angiotensin-(1–7) inhibits tumor growth via autophagy by downregulating PI3K/Akt/mTOR signaling in human nasopharyngeal carcinoma xenografts - Yu-Tsai Lin; Hung-Chen Wang; Hui-Ching Chuang; Yi-Chiang Hsu; Ming-Yu Yang; Chih-Yen Chien (Journal of Molecular Medicine, 2018)

Asian dust storms and diabetes hospitalization: a nationwide population-based study - Yun-Shan Chan; Joshua Chen-Yuan Teng; Tsai-Ching Liu; Yu-I Peng (Air Quality, Atmosphere & Health, 2018)

Exercise Rehabilitation Attenuates Cognitive Deficits in Rats with Traumatic Brain Injury by Stimulating the Cerebral HSP20/BDNF/TrkB Signalling Axis - Willy Chou; Yu-Fan Liu; Cheng-Hsien Lin; Mao-Tsun Lin; Chi-Chun Chen; Wen-Pin Liu; Ching-Ping Chang; Chung-Ching Chio (Molecular Neurobiology, 2018)

Web-Based Experience Sharing Platform on Medical Device Incidents for Clinical Engineers in Hospitals - Mei-Fen Chen; Cheng-Lun Tsai; Yung-Hsin Chen; Yu-Wen Huang; Cheng-Ning Wu; Ching Chou; Chia-Hung Chien; Pei-Weng Tu; Tsair Kao; Kang-Ping Lin (Journal of Medical and Biological Engineering, 2018)

Unexpected dose response of HaCaT to UVB irradiation - Rong-Shing Chang; Chi-Shuo Chen; Ching-Lung Huang; Chiu-Ting Chang; Yujia Cui; Wei-Ju Chung; Wun-Yi Shu; Chi-Shiun Chiang; Chun-Yu Chuang; Ian C. Hsu (In Vitro Cellular & Developmental Biology - Animal, 2018)

Effects of normoxic and hypoxic exercise training on the bactericidal capacity and subsequent apoptosis of neutrophils in sedentary men - Yi-Ching Chen; Wan-Yu Chou; Tieh-Cheng Fu; Jong-Shyan Wang (European Journal of Applied Physiology, 2018)

Occurrence of Emerging Contaminants in Aquaculture Waters: Cross-Contamination between Aquaculture Systems and Surrounding Waters - Webber Wei-Po Lai; Yen-Ching Lin; Yu-Hsiang Wang; Yue Leon Guo; Angela Yu-Chen Lin (Water, Air, & Soil Pollution, 2018)

Protein-bounded uremic toxin p-cresylsulfate induces vascular permeability alternations - Wei-Hua Tang; Chao-Ping Wang; Teng-Hung Yu; Pei-Yang Tai; Shih-Shin Liang; Wei-Chin Hung; Cheng-Ching Wu; Sung-Hao Huang; Yau-Jiunn Lee; Shih-Chieh Chen (Histochemistry and Cell Biology, 2018)

Improving the management of Taiwanese fishery resource conservation zones based on public perceptions and willingness to pay for ecosystem services - Jyun-Long Chen; Yu-Sheng Lin; Ching-Ta Chuang (Journal of Coastal Conservation, 2018)

Epirubicin induces apoptosis in osteoblasts through death-receptor and mitochondrial pathways - Tzu-Ching Huang; Pu-Rong Chiu; Wen-Tsan Chang; Bau-Shan Hsieh; Yu-Ci Huang; Hsiao-Ling Cheng; Li-Wen Huang; Yu-Chen Hu; Kee-Lung Chang (Apoptosis, 2018)

Finite Element Analysis of Tongue Type Calcaneal Fracture with Open Reduction and Internal Fixation with Locking Plate - Ching-Hsuan Chen; Yu-Hsuan Huang; Chinghua Hung; Chen-Sheng Chen; Chao-Ching Chiang (Journal of Medical and Biological Engineering, 2018)

The persistence and photostabilizing characteristics of benzotriazole and 5-methyl-1H-benzotriazole reduce the photochemical behavior of common photosensitizers and organic compounds in aqueous environments - Kenneth Hsien-Yung Chung; Yen-Ching Lin; Angela Yu-Chen Lin (Environmental Science and Pollution Research, 2018)

Photolytic degradation of ciprofloxacin in solid and aqueous environments: kinetics, phototransformation pathways, and byproducts - Yen-Ching Lin; Kuan-Wen Hsiao; Angela Yu-Chen Lin (Environmental Science and Pollution Research, 2018)

Prevalence, mechanisms and genetic relatedness of the human pathogenic fungus Aspergillus fumigatus exhibiting resistance to medical azoles in the environment of Taiwan - Hsuan‐Chen Wang; Jui‐Chang Huang; Yong‐Hong Lin; Yu‐Hsin Chen; Ming‐I Hsieh; Pui‐Ching Choi; Hsiu‐Jung Lo; Wei‐Lun Liu; Ching‐Shan Hsu; Hsin‐I Shih; Chi‐Jung Wu; Yee‐Chun Chen (Environmental Microbiology, 2018)
Summary Emerging azole resistance in Aspergillus fumigatus poses a serious threat to human health. This nationwide surveillance study investigated the prevalence and molecular characteristics of azole‐resistant A. fumigatus environmental isolates in Taiwan, an island country with increasing use of azole fungicides. Of the 2760 air and soil samples screened from 2014 to 2016, 451 A. fumigatus isolates were recovered from 266 samples and 34 isolates from 29 samples displayed resistance to medical azoles (itraconazole, voriconazole or posaconazole). The resistance prevalence was 10.9% and 7.5% in A. fumigatus ‐positive samples and isolates respectively. Most (29, 85.3%) azole‐resistant isolates harboured TR 34 /L98H mutations, which were widely distributed, clustered genetically with clinical isolates, and had growth rates that were similar to those of the wild‐type isolates. Microsatellite genotyping revealed both the global spread of the TR 34 /L98H isolates and the occurrence of TR 34 /L98H/S297T/F495I isolates belonging to local microsatellite genotypes. AfuMDR3 and atrF , two efflux transporter genes, were constitutively upregulated in two individual resistant isolates without cyp51A mutations, highlighting their potential roles in azole resistance. These results emphasize the need for periodic environmental surveillance at the molecular level in regions in which azole fungicides are applied, and agricultural fungicide management strategies that generate less selective pressure should be investigated.

Unprecedented calcareous algal reefs in northern Taiwan merit high conservation priority - Ching-Yu Liou; Sung-Yin Yang; Chaolun Allen Chen (Coral Reefs, 2017)

Biomechanical evaluation of reconstruction plates with locking, nonlocking, and hybrid screws configurations in calcaneal fracture: a finite element model study - Ching-Hsuan Chen; Chinghua Hung; Yu-Chun Hsu; Chen-Sheng Chen; Chao-Ching Chiang (Medical & Biological Engineering & Computing, 2017)

Cytoplasmic aryl hydrocarbon receptor regulates glycogen synthase kinase 3 beta, accelerates vimentin degradation, and suppresses epithelial–mesenchymal transition in non-small cell lung cancer cells - Ching-Hao Li; Chen-Wei Liu; Chi-Hao Tsai; Yi-Jen Peng; Yu-Hsuan Yang; Po-Lin Liao; Chen-Chen Lee; Yu-Wen Cheng; Jaw-Jou Kang (Archives of Toxicology, 2017)

A novel study of artificial bee colony with clustering technique on paddy rice image classification - Shiuan Wan; Shih-Hsun Chang; Ching-Tung Peng; Yu-Keng Chen (Arabian Journal of Geosciences, 2017)

p-Hydroxyacetophenone suppresses nuclear factor-κB-related inflammation in nociceptive and inflammatory animal models - Chang Ching-Wen; Chen Yun-Chieh; Lin Yu-Chin; Peng Wen-Huang (Journal of Natural Medicines, 2017)

An ENSO prediction approach based on ocean conditions and ocean–atmosphere coupling - Yu-heng Tseng; Zeng-Zhen Hu; Ruiqiang Ding; Han-ching Chen (Climate Dynamics, 2017)

Status quo of management of the human tissue banks in Taiwan - Ching-Pang Chou; Szu-Cheng Chou; Ying-Hua Chen; Yu-Hsuan Chen; Ming-Shin Lee (Cell and Tissue Banking, 2017)

Estimation of students’ exposure to metal concentrations from river-dust episodes during 1994–2012 - Hao-Jan Yang; Szu-Chieh Chen; Chiung-Wen Hu; Yi-Chen Chiang; Ching-Tsan Tsai; Pin-Yu Lin; Dian-Jheng Lai; Chung-Yih Kuo (Environmental Science and Pollution Research, 2017)

Health risk assessment of groundwater arsenic pollution in southern Taiwan - Ching-Ping Liang; Sheng-Wei Wang; Yu-Hsuan Kao; Jui-Sheng Chen (Environmental Geochemistry and Health, 2016)

Indoxyl sulfate enhances IL-1β-induced E-selectin expression in endothelial cells in acute kidney injury by the ROS/MAPKs/NFκB/AP-1 pathway - Wen-Ching Shen; Chan-Jung Liang; Tao-Ming Huang; Chen-Wei Liu; Shu-Huei Wang; Guang-Huar Young; Jaw-Shiun Tsai; Ying-Chin Tseng; Yu-Sen Peng; Vin-Cent Wu; Yuh-Lien Chen (Archives of Toxicology, 2016)

CLEC5A is critical for dengue virus-induced osteoclast activation and bone homeostasis - Ya-Lang Huang; Szu-Ting Chen; Ren-Shyan Liu; Yen-Hsu Chen; Chun-Yu Lin; Chung-Hao Huang; Pei-Yun Shu; Ching-Len Liao; Shie-Liang Hsieh (Journal of Molecular Medicine, 2016)

Curcumin downregulates p38 MAPK-dependent X-ray repair cross-complement group 1 (XRCC1) expression to enhance cisplatin-induced cytotoxicity in human lung cancer cells - Chun-Liang Tung; Yi-Jun Jian; Jyh-Cheng Chen; Tai-Jing Wang; Wen-Ching Chen; Hao-Yu Zheng; Po-Yuan Chang; Kai-Sheng Liao; Yun-Wei Lin (Naunyn-Schmiedeberg's Archives of Pharmacology, 2016)

Molecular Characterization of Ethylene Response Sensor 1 (BoERS1) in Bambusa oldhamii - Yi-Lin Hsieh; Ching-Fang Lu; Bing-Yu Chiang; Shu-Chien Liao; Rita P.-Y. Chen; Choun-Sea Lin; Ai-Yu Wang; Chien-Chih Yang (Plant Molecular Biology Reporter, 2016)

Sensory determinants of valve rhythm dynamics provide in situ biodetection of copper in aquatic environments - Li-John Jou; Bo-Ching Chen; Wei-Yu Chen; Chung-Min Liao (Environmental Science and Pollution Research, 2016)

Microsatellite records for volume 8, issue 1 - Maria Cristina Arias; Stéphane Aulagnier; Erin F. Baerwald; Robert M. R. Barclay; Jacqueline Silva Batista; Rochelle R. Beasley; Rodrigo A. Bezerra; Frédéric Blanc; Eli S. Bridge; Maria Teresa Cabria; Lívia Izabela Caputo; Jie Chen; et al. (Conservation Genetics Resources, 2016)

Erratum to: Soluble organic C and N and their relationships with soil organic C and N and microbial characteristics in moso bamboo (Phyllostachys edulis) plantations along an elevation gradient in Central Taiwan - Ching-Yu Huang; Shih-Hao Jien; Tsai-Huei Chen; Guanglong Tian; Chih-Yu Chiu (Journal of Soils and Sediments, 2016)

Multiobjective Optimal Design of Sewerage Rehabilitation by Using the Nondominated Sorting Genetic Algorithm-II - Yu-Hao Lin; Yi-Ping Chen; Ming-Der Yang; Tung-Ching Su (Water Resources Management, 2016)

G206D Mutation of Presenilin-1 Reduces Pen2 Interaction, Increases Aβ42/Aβ40 Ratio and Elevates ER Ca2+ Accumulation - Wei-Ting Chen; Yi-Fang Hsieh; Yan-Jing Huang; Che-Ching Lin; Yen-Tung Lin; Yu-Chao Liu; Cheng-Chang Lien; Irene Han-Juo Cheng (Molecular Neurobiology, 2015)

Intra-Colonial Functional Differentiation-Related Modulation of the Cellular Membrane in a Pocilloporid Coral Seriatopora caliendrum - Chuan-Ho Tang; Ping-Chang Ku; Ching-Yu Lin; Te-Hao Chen; Kuo-Hsin Lee; Shu-Hui Lee; Wei-Hsien Wang (Marine Biotechnology, 2015)

Synergistic Impact of Nicotine and Shear Stress Induces Cytoskeleton Collapse and Apoptosis in Endothelial Cells - Yu-Hsiang Lee; Ruei-Siang Chen; Nen-Chung Chang; Kueir-Rarn Lee; Chien-Tsai Huang; Yu-Ching Huang; Feng-Ming Ho (Annals of Biomedical Engineering, 2015)

Associations between TRPV4 genotypes and body mass index in Taiwanese subjects - De-Min Duan; Semon Wu; Lung-An Hsu; Ming-Sheng Teng; Jeng-Feng Lin; Yu-Chen Sun; Ching-Feng Cheng; Yu-Lin Ko (Molecular Genetics and Genomics, 2015)

The differential roles of Slit2-exon 15 splicing variants in angiogenesis and HUVEC permeability - Yun-Chiu Yang; Pei-Ni Chen; Siou-Yu Wang; Chen-Yi Liao; Yu-Ying Lin; Shih-Rhong Sun; Chun-Ling Chiu; Yih-Shou Hsieh; Jia-Ching Shieh; Jinghua Tsai Chang (Angiogenesis, 2015)

Occurrence of pharmaceuticals, hormones, and perfluorinated compounds in groundwater in Taiwan - Yen-Ching Lin; Webber Wei-Po Lai; Hsin-hsin Tung; Angela Yu-Chen Lin (Environmental Monitoring and Assessment, 2015)

Analysis of space–time patterns of rainfall events during 1996–2008 in Yilan County (Taiwan) - Hwa-Lung Yu; Bo-Lin Chen; Chuan-Hung Chiu; Mong-Ming Lu; Ching-pin Tung (Stochastic Environmental Research and Risk Assessment, 2015)

Methodology of disaster risk assessment for debris flows in a river basin - Ing-Jia Chiou; Ching-Ho Chen; Wei-Lin Liu; Shiao-Mei Huang; Yu-Min Chang (Stochastic Environmental Research and Risk Assessment, 2015)

The Akt inhibitor MK-2206 enhances the cytotoxicity of paclitaxel (Taxol) and cisplatin in ovarian cancer cells - Ying-Hsi Lin; Bert Yu-Hung Chen; Wei-Ting Lai; Shao-Fu Wu; Jih-Hwa Guh; Ann-Lii Cheng; Lih-Ching Hsu (Naunyn-Schmiedeberg's Archives of Pharmacology, 2015)

Allyl isothiocyanate (AITC) inhibits pregnane X receptor (PXR) and constitutive androstane receptor (CAR) activation and protects against acetaminophen- and amiodarone-induced cytotoxicity - Yun-Ping Lim; Ching-Hao Cheng; Wei-Cheng Chen; Shih-Yu Chang; Dong-Zong Hung; Jih-Jung Chen; Lei Wan; Wei-Chih Ma; Yu-Hsien Lin; Cing-Yu Chen; Tsuyoshi Yokoi; Miki Nakajima; et al. (Archives of Toxicology, 2015)

Spatial distribution of soil erosion and suspended sediment transport rate for Chou-Shui river basin - Chin-Ping Lin; Ching-Nuo Chen; Yu-Min Wang; Chih-Heng Tsai; Chang-Tai Tsai (Journal of Earth System Science, 2014)

Maintenance of human adipose derived stem cell (hASC) differentiation capabilities using a 3D culture - Ching-Yu Lin; Chi-Hui Huang; Yuan-Kun Wu; Nai-Chen Cheng; Jiashing Yu (Biotechnology Letters, 2014)

Soluble organic C and N and their relationships with soil organic C and N and microbial characteristics in moso bamboo (Phyllostachys edulis) plantations along an elevation gradient in Central Taiwan - Ching-Yu Huang; Shih-Hao Jien; Tsai-Huei Chen; Guanglong Tian; Chih-Yu Chiu (Journal of Soils and Sediments, 2014)

The dual functions of YAP-1 to promote and inhibit cell growth in human malignancy - Hai Wang; Yu-Chen Du; Xiao-jun Zhou; Hong Liu; Shou-Ching Tang (Cancer and Metastasis Reviews, 2014)

Terfenadine induces anti-proliferative and apoptotic activities in human hormone-refractory prostate cancer through histamine receptor-independent Mcl-1 cleavage and Bak up-regulation - Wei-Ting Wang; Yen-Hui Chen; Jui-Ling Hsu; Wohn-Jenn Leu; Chia-Chun Yu; She-Hung Chan; Yunn-Fang Ho; Lih-Ching Hsu; Jih-Hwa Guh (Naunyn-Schmiedeberg's Archives of Pharmacology, 2014)

Determination of homogeneous regions for regional reference evapotranspiration estimation using the self-organizing map in western Taiwan - Ching-Tien Chen; Yu-Chuan Chang; Guan-Ting Wu (Paddy and Water Environment, 2014)

Functional Investigation of Transmembrane Helix 3 in H+-Translocating Pyrophosphatase - Ching-Hung Lee; Yen-Wei Chen; Yun-Tzu Huang; Yih-Jiuan Pan; Chien-Hsien Lee; Shih-Ming Lin; Lin-Kun Huang; Yueh-Yu Lo; Yu-Fen Huang; Yu-Di Hsu; Shih-Chung Yen; Jenn-Kang Hwang; et al. (The Journal of Membrane Biology, 2013)

Pemetrexed downregulates ERCC1 expression and enhances cytotoxicity effected by resveratrol in human nonsmall cell lung cancer cells - Ruey-Shyang Chen; Jen-Chung Ko; Hsien-Chun Chiu; Ting-Yu Wo; Yi-Jhen Huang; Sheng-Chieh Tseng; Huang-Jen Chen; Yu-Ching Huang; Yi-Jun Jian; Wei-Ting Lee; Yun-Wei Lin (Naunyn-Schmiedeberg's Archives of Pharmacology, 2013)

Design, synthesis, and evaluation of fluorescent cell-penetrating peptidic antagonists of Grb2-SH2 for targeting MCF-7 breast cancer cells - Yu-Cheng Hsiao; Chen-Yu Lee; Yi-Jhen Lin; Shu-Huai Tsai; Kee-Ching G. Jeng; Wei-Ting Chao; Feng-Di T. Lung (Medicinal Chemistry Research, 2013)

Subneutralizing antibodies to enterovirus 71 induce antibody-dependent enhancement of infection in newborn mice - I-Chun Chen; Shih-Min Wang; Chun-Keung Yu; Ching-Chuan Liu (Medical Microbiology and Immunology, 2013)

Toxicokinetics of tilapia following high exposure to waterborne and dietary copper and implications for coping mechanisms - Jeng-Wei Tsai; Yun-Ru Ju; Ying-Hsuan Huang; Yue-Sun Deng; Wei-Yu Chen; Chin-Ching Wu; Chung-Min Liao (Environmental Science and Pollution Research, 2013)

Hyperinakin, a new anti-inflammatory phloroglucinol derivative from Hypericum nakamurai - Yuan-Bin Cheng; Ahmed Eid Fazary; Yu-Chi Lin; I-Wen Lo; Seow-Chin Ong; Shun-Ying Chen; Ching-Te Chien; Yen-Jung Lin; Wan-Wan Lin; Ya-Ching Shen (Natural Product Research, 2013)

Transcriptional regulation of tristetraprolin by NF-κB signaling in LPS-stimulated macrophages - Yu-Ling Chen; Yu-Wun Jiang; Yu-Lun Su; Sheng-Chung Lee; Mau-Sun Chang; Ching-Jin Chang (Molecular Biology Reports, 2013)

The enhancement of biofilm formation in Group B streptococcal isolates at vaginal pH - Yueh-Ren Ho; Chien-Ming Li; Chen-Hsiang Yu; Yuh-Jyh Lin; Ching-Ming Wu; I-Chen Harn; Ming-Jer Tang; Yi-Ting Chen; Fang-Chi Shen; Chien-Yi Lu; Tai-Chun Tsai; Jiunn-Jong Wu (Medical Microbiology and Immunology, 2013)

A study of the frequency of methylation of gene promoter regions in colorectal cancer in the Taiwanese population - CHANG-CHIEH WU; JEN-CHUN KUAN; CHIH-HSIUNG HSU; TZU-AN CHEN; CHIEN-AN SUN; TSAN YANG; SHINN-LONG LIN; YU-CHING CHOU (Journal of Genetics, 2013)

Glycogen synthase kinase-3β inactivation is an intracellular marker and regulator for endotoxemic neutrophilia - Tsan-Tzu Yang; Chia-Ling Chen; Wei-Chieh Lin; Yee-Shin Lin; Po-Chun Tseng; Chia-Yuan Hsieh; Yu-Hong Chen; Wei-Ching Huang; Cheng-Chieh Tsai; Chi-Yun Wang; Chi-Chang Shieh; Chiou-Feng Lin (Journal of Molecular Medicine, 2013)

A molecular diagnosis method using real-time PCR for quantification and detection of Fusarium oxysporum f. sp. cubense race 4 - Ying-Hong Lin; Ching-Chung Su; Chih-Ping Chao; Chi-Yu Chen; Chung-Jan Chang; Jenn-Wen Huang; Pi-Fang Linda Chang (European Journal of Plant Pathology, 2013)

Isolation of marine bacteria with antimicrobial activities from cultured and field-collected soft corals - Yu-Hsin Chen; Jimmy Kuo; Ping-Jung Sung; Yu-Chia Chang; Mei-Chin Lu; Tit-Yee Wong; Jong-Kang Liu; Ching-Feng Weng; Wen-Hung Twan; Fu-Wen Kuo (World Journal of Microbiology and Biotechnology, 2012)

Recombined sequences between the non-coding control regions of JC and BK viruses found in the urine of a renal transplantation patient - Yu-Ching Liaw; Cheng-Hsu Chen; Kuo-Hsiung Shu; Chiung-Yao Fang; Wei-Chih Ou; Pei-Lain Chen; Cheng-Huang Shen; Mien-Chun Lin; Deching Chang; Meilin Wang (Virus Genes, 2012)

Albumin prevents reactive oxygen species-induced mitochondrial damage, autophagy, and apoptosis during serum starvation - Shu-Yu Liu; Chia-Ling Chen; Tsan-Tzu Yang; Wei-Ching Huang; Chia-Yuan Hsieh; Wan-Jou Shen; Tsung-Ting Tsai; Chi-Chang Shieh; Chiou-Feng Lin (Apoptosis, 2012)

In vivo screening of zebrafish microRNA responses to bacterial infection and their possible roles in regulating immune response genes after lipopolysaccharide stimulation - Tsung-Han Wu; Chieh-Yu Pan; Ming-Ching Lin; Jung-Chen Hsieh; Cho-Fat Hui; Jyh-Yih Chen (Fish Physiology and Biochemistry, 2012)

Interplay of RsbM and RsbK controls the σ B activity of Bacillus cereus - Lei‐Chin Chen; Jung‐Chi Chen; Jwu‐Ching Shu; Chien‐Yen Chen; Ssu‐Ching Chen; Shu‐Hwa Chen; Chun‐Yen Lin; Chi‐Yu Lu; Chien‐Cheng Chen (Environmental Microbiology, 2012)
Summary The alternative transcription factor σ B of Bacillus cereus controls the expression of a number of genes that respond to environmental stress. Four proteins encoded in the sigB gene cluster, including RsbV, RsbW, RsbY (RsbU) and RsbK, are known to be essential in the σ B ‐mediated stress response. In the context of stress, the hybrid sensor kinase RsbK is thought to phosphorylate the response regulator RsbY, a PP2C serine phosphatase, leading to the dephosphorylation of the phosphorylated RsbV. The unphosphorylated RsbV then sequesters the σ B antagonist, RsbW, ultimately liberating σ B . The gene arrangement reveals an open reading frame, bc1007 , flanked immediately downstream by rsbK within the sigB gene cluster. However, little is known about the function of bc1007 . In this study, the deletion of bc1007 resulted in high constitutive σ B expression independent of environmental stimuli, indicating that bc1007 plays a role in σ B regulation. A bacterial two‐hybrid analysis demonstrated that BC1007 interacts directly with RsbK, and autoradiographic studies revealed a specific C 14 ‐methyl transfer from the radiolabelled S‐adenosylmethionine to RsbK when RsbK was incubated with purified BC1007. Our data suggest that BC1007 (RsbM) negatively regulates σ B activity by methylating RsbK. Additionally, mutagenic substitution was employed to modify 12 predicted methylation residues in RsbK. Certain RsbK mutants were able to rescue σ B activation in a rsbK ‐deleted bacterial strain, but RsbK E439A failed to activate σ B , and RsbK E446A only moderately induced σ B . These results suggest that Glu439 is the preferred methylation site and that Glu446 is potentially a minor methylation site. Gene arrays of the rsbK orthologues and the neighbouring rsbM orthologues are found in a wide range of bacteria. The regulation of sigma factors through metylation of RsbK‐like sensor kinases appears to be widespread in the microbial world.

Copper accumulation, translocation, and toxic effects in grapevine cuttings - Kai-Wei Juang; Yung-I Lee; Hung-Yu Lai; Chiung-Huei Wang; Bo-Ching Chen (Environmental Science and Pollution Research, 2012)

Toxicokinetics/toxicodynamics with damage feedback improves risk assessment for tilapia and freshwater clam exposed to arsenic - Wei-Yu Chen; Chung-Min Liao; Yun-Ru Ju; Sher Singh; Li-John Jou; Bo-Ching Chen; Jeng-Wei Tsai (Ecotoxicology, 2012)

Identification of secretory gelsolin as a plasma biomarker associated with distant organ metastasis of colorectal cancer - Ming-Hung Tsai; Chih-Ching Wu; Pei-Hua Peng; Ying Liang; Yung-Chin Hsiao; Kun-Yi Chien; Jeng-Ting Chen; Shin-Jie Lin; Rei-Ping Tang; Ling-Ling Hsieh; Jau-Song Yu (Journal of Molecular Medicine, 2012)

Investigations into the Correlation Properties of Membrane Electroporation-Induced Inward Currents: Prediction of Pore Formation - Sheng-Nan Wu; Chia-Chen Yeh; Pei-Yu Wu; Hsien-Ching Huang; Mei-Ling Tsai (Cell Biochemistry and Biophysics, 2012)

Infectious bursal disease DNA vaccination conferring protection by delayed appearance and rapid clearance of invading viruses - Yung-Yi Chen; Ming Kun Hsieh; Chun-Yu Tung; Ching Ching Wu; Tsang Long Lin (Archives of Virology, 2011)

Mean Structure and Variability of the Cold Dome Northeast of Taiwan - Sen Jan; Chung-Chi Chen; Ya-Ling Tsai; Yiing Jiang Yang; Joe Wang; Ching-Sheng Chern; Glen Gawarkiewicz; Ren-Chieh Lien; Luca Centurioni; Jia-Yu Kuo (Oceanography, 2011)

Perturbations of the stress-induced GLUT4 localization pathway in slow-twitch muscles of obese Zucker rats - Yu-Ching Chen; Shin-Da Lee; Shin-Ying Hsih; Yung-Pei Hsu; Chia-Hua Kuo; Low-Tone Ho (Journal of Physiology and Biochemistry, 2011)

Coupling bioaccumulation and phytotoxicity to predict copper removal by switchgrass grown hydroponically - Kai-Wei Juang; Hung-Yu Lai; Bo-Ching Chen (Ecotoxicology, 2011)

Assessing abalone growth inhibition risk to cadmium and silver by linking toxicokinetics/toxicodynamics and subcellular partitioning - Wei-Yu Chen; Yun-Ru Ju; Bo-Ching Chen; Jeng-Wei Tsai; Chia-Jung Lin; Chung-Min Liao (Ecotoxicology, 2011)

Characterization and prediction of mRNA polyadenylation sites in human genes - Tzu-Hao Chang; Li-Ching Wu; Yu-Ting Chen; Hsien-Da Huang; Baw-Jhiune Liu; Kuang-Fu Cheng; Jorng-Tzong Horng (Medical & Biological Engineering & Computing, 2011)

Generation of transgenic watermelon resistant to Zucchini yellow mosaic virus and Papaya ringspot virus type W - Tsong-Ann Yu; Chu-Hui Chiang; Hui-Wen Wu; Chin-Mei Li; Ching-Fu Yang; Jun-Han Chen; Yu-Wen Chen; Shyi-Dong Yeh (Plant Cell Reports, 2011)

Enhancement of temozolomide-induced apoptosis by valproic acid in human glioma cell lines through redox regulation - Ching-Hsein Chen; Yu-Jia Chang; Maurice S. B. Ku; King-Thom Chung; Jen-Tsung Yang (Journal of Molecular Medicine, 2011)

Using chemical fractionation to evaluate the phytoextraction of cadmium by switchgrass from Cd-contaminated soils - Bo-Ching Chen; Hung-Yu Lai; Dar-Yuan Lee; Kai-Wei Juang (Ecotoxicology, 2011)

Activity enhancement and stabilization of lipase from Pseudomonas cepacia in polyallylamine-mediated biomimetic silica - Guan-Chun Chen; I-Ching Kuan; Jian-Ren Hong; Bing-Hong Tsai; Shiow-Ling Lee; Chi-Yang Yu (Biotechnology Letters, 2011)

Association between human papillomavirus and adenocarcinoma of rectum and recto-sigmoid junction: a cohort study of 10,612 women in Taiwan - Li-Chung Chuang; Hui-Chi Chen; San-Lin You; Ching-Yu Lin; Mei-Hung Pan; Yi-Chun Chou; Chang-Yao Hsieh; Chien-Jen Chen (Cancer Causes & Control, 2010)

Constitutive expression of a fungal glucose oxidase gene in transgenic tobacco confers chilling tolerance through the activation of antioxidative defence system - Subbiyan Maruthasalam; Yi Lun Liu; Ching Mei Sun; Pei Ying Chen; Chih Wen Yu; Pei Fang Lee; Chin Ho Lin (Plant Cell Reports, 2010)

Role of DNA methyltransferase 1 in hormone-resistant prostate cancer - Miao-Fen Chen; Wen-Cheng Chen; Yu-Jia Chang; Ching-Fang Wu; Chun-Te Wu (Journal of Molecular Medicine, 2010)

5,5-Diphenyl-2-thiohydantoin-N10 (DPTH-N10) suppresses proliferation of cultured colon cancer cell line COLO-205 by inhibiting DNA synthesis and activating apoptosis - Tong-Sheng Lee; Li-Ching Chen; Yuan Liu; Jender Wu; Yu-Chih Liang; Wen-Sen Lee (Naunyn-Schmiedeberg's Archives of Pharmacology, 2010)

Porcine lactoferrin as feedstuff additive elevates avian immunity and potentiates vaccination - Che-Ming Hung; Shinn-Chih Wu; Chih-Ching Yen; Ming-Fong Lin; Yi-Wen Lai; Yu-Tang Tung; Hsiao-Ling Chen; Chuan-Mu Chen (BioMetals, 2010)

Probiotic Lactobacillus casei Expressing Human Lactoferrin Elevates Antibacterial Activity in the Gastrointestinal Tract - Hsiao-Ling Chen; Yi-Wen Lai; Chua-Shun Chen; Te-Wei Chu; Willie Lin; Chih-Ching Yen; Ming-Fong Lin; Ming-Yu Tu; Chuan-Mu Chen (BioMetals, 2010)

Design and implementation of an adaptive code discriminator in a DSP/FPGA-based Galileo receiver - Jyh-Ching Juang; Yu-Hsuan Chen; Tsai-Ling Kao; Yung-Fu Tsai (GPS Solutions, 2010)

Early-life or lifetime sun exposure, sun reaction, and the risk of squamous cell carcinoma in an Asian population - Yen-Ching Chen; David C. Christiani; Huey-Jen Jenny Su; Yu-Mei Hsueh; Thomas J. Smith; Louise M. Ryan; Sheau-Chiou Chao; Julia Yu-Yun Lee; Yue-Liang Leon Guo (Cancer Causes & Control, 2010)

Ploidy doubling by in vitro culture of excised protocorms or protocorm-like bodies in Phalaenopsis species - Wen Huei Chen; Ching Yan Tang; Yu Lin Kao (Plant Cell, Tissue and Organ Culture (PCTOC), 2009)

Serial cytokine levels in patients with severe sepsis - Huang-Pin Wu; Chian-Kuang Chen; Kong Chung; Jo-Chi Tseng; Chung-Ching Hua; Yu-Chih Liu; Duen-Yau Chuang; Chung-Han Yang (Inflammation Research, 2009)

A new flavonol galloylrhamnoside and a new lignan glucoside from the leaves of Koelreuteria henryi Dummer - Tzong-Huei Lee; Yuan-Hsiang Chiang; Chin-Hui Chen; Pi-Yu Chen; Ching-Kuo Lee (Journal of Natural Medicines, 2009)

A biotic ligand model-based toxicodynamic approach to predict arsenic toxicity to tilapia gills in cultural ponds - Bo-Ching Chen; Wei-Yu Chen; Chung-Min Liao (Ecotoxicology, 2009)

Development of a Methodology for Strategic Environmental Assessment: Application to the Assessment of Golf Course Installation Policy in Taiwan - Ching-Ho Chen; Ray-Shyan Wu; Wei-Lin Liu; Wen-Ray Su; Yu-Min Chang (Environmental Management, 2009)

Estimating the economic impacts of climate change on infectious diseases: a case study on dengue fever in Taiwan - Wei-Chun Tseng; Chi-Chung Chen; Ching-Cheng Chang; Yu-Hsien Chu (Climatic Change, 2009)

Fruit Development, Ripening and Quality Related Genes in the Papaya Genome - Robert E. Paull; Beth Irikura; Pingfang Wu; Helen Turano; Nancy Jung Chen; Andrea Blas; John K. Fellman; Andrea R. Gschwend; Ching Man Wai; Qingyi Yu; Gernot Presting; Maqsudul Alam; et al. (Tropical Plant Biology, 2008)

Characteristics analysis for the flash flood-induced debris flows - Chen Chien-Yuan; Chen Lien-Kuang; Yu Fan-Chieh; Lin Sheng-Chi; Lin Yu-Ching; Lee Chou-Lung; Wang Yu-Ting; Cheung Kei-Wai (Natural Hazards, 2008)

Time to rehospitalization in patients with bipolar I disorder on lithium or valproate with adjunctive antipsychotics - Ching-Hua Lin; Ching-Wen Huang; Cheng-Chung Chen; Yu-Fen Hsu; Wen-Ho Chang; Hsien-Yuan Lane (Psychopharmacology, 2008)

Possible involvement of MAP kinase pathways in acquired metal-tolerance induced by heat in plants - Po-Yu Chen; Kuo-Ting Lee; Wen-Chang Chi; Heribert Hirt; Ching-Chun Chang; Hao-Jen Huang (Planta, 2008)

Gene expression variation increase in trisomy 21 tissues - Ching Yu Chou; Li Yu Liu; Chien Yu Chen; Cheng Hsien Tsai; Hsiao Lin Hwa; Li Yun Chang; Yi Shing Lin; Fon Jou Hsieh (Mammalian Genome, 2008)

Solubilization of inorganic phosphates and plant growth promotion by Aspergillus niger - Chun-Chao Chuang; Yu-Lin Kuo; Chen-Ching Chao; Wei-Liang Chao (Biology and Fertility of Soils, 2007)

Lignans and anthraquinones from the fruits of Morinda citrifolia - Chwan Fwu Lin; Ching Li Ni; Yu Ling Huang; Shuenn Jyi Sheu; Chien Chih Chen (Natural Product Research, 2007)

Two new xeniolides from a Taiwanese Xenia soft coral - Ya-Ching Shen; Yu-Hui Chen; Yuan-Bin Cheng; Yao Haur Kuo; Ashraf Taha Khalil (Natural Product Research, 2007)

A rice phenomics study—phenotype scoring and seed propagation of a T-DNA insertion-induced rice mutant population - Chyr-Guan Chern; Ming-Jen Fan; Su-May Yu; Ai-Ling Hour; Po-Chang Lu; Yao-Cheng Lin; Fu-Jin Wei; Sheng-Chung Huang; Shu Chen; Ming-Hsing Lai; Ching-Shan Tseng; Hsing-Mu Yen; et al. (Plant Molecular Biology, 2007)

Development of a molecular marker for a bruchid (Callosobruchus chinensis L.) resistance gene in mungbean - Huei-Mei Chen; Chien-An Liu; C. George Kuo; Ching-Mei Chien; Horng-Chi Sun; Chung-Chu Huang; Yu-Chung Lin; Hsin-Mei Ku (Euphytica, 2007)

Solubilization of inorganic phosphates and plant growth promotion by Aspergillus niger - Chun-Chao Chuang; Yu-Lin Kuo; Chen-Ching Chao; Wei-Liang Chao (Biology and Fertility of Soils, 2007)

A web-based decision support system for slopeland hazard warning - Yu Fan-Chieh; Chen Chien-Yuan; Lin Sheng-Chi; Lin Yu-Ching; Wu Shang-Yu; Cheung Kei-Wai (Environmental Monitoring and Assessment, 2007)

A rice gene activation/knockout mutant resource for high throughput functional genomics - Yue-Ie Hsing; Chyr-Guan Chern; Ming-Jen Fan; Po-Chang Lu; Ku-Ting Chen; Shuen-Fang Lo; Peng-Kai Sun; Shin-Lon Ho; Kuo-Wei Lee; Yi-Chieh Wang; Wen-Lii Huang; Swee-Suak Ko; et al. (Plant Molecular Biology, 2007)

Enhancement of water storage capacity in wetland rice fields through deepwater management practice - Yu‐Chuan Chang; Chun‐E. Kan; Ching‐Tien Chen; Sheng‐Feng Kuo (Irrigation and Drainage, 2007)
Paddy field storage of rainfall by bunds is like a rainwater cistern system during the rainy season. Deepwater management practice in paddy fields might be good for rice production and water storage capacity at the same time. The study was conducted in an experiment testing two water management treatments with six rice variety treatments using two lysimeter experiments. The results revealed that deepwater management significantly affected rice production. On the other hand, deepwater management increased the effective rainfall (70 mm) and percolation (225 mm). The runoff coefficient under deepwater management decreased from 0.67 to 0.53. It was reasonable to conclude that the deepwater management provided more water storage capacity during the growing season. Finally, water productivity results point out that even though the volume of input water under deepwater management had increased, deepwater management still can generate higher water productivity. It looks as if it is pointless to save water during the rainy season. On the contrary, if excess water is available in rivers, it should be delivered in timely fashion to the wetland rice fields to increase effective rainfall and the excess saved by maintaining adequate percolation to replenish groundwater, without having to follow strict water conservation measures. Copyright © 2007 John Wiley & Sons, Ltd.

Improving debris flow monitoring in Taiwan by using high-resolution rainfall products from QPESUMS - Chien-Yuan Chen; Lee-Yao Lin; Fan-Chieh Yu; Ching-Sheng Lee; Chun-Chieh Tseng; An-Hsiang Wang; Kei-Wai Cheung (Natural Hazards, 2007)

Organization and promoter analysis of a tiger shrimp Penaeus monodon single WAP domain-containing protein gene - Jyh Yih CHEN; Jian Chyi CHEN; Sheng Hwa LIN; Chia Yu PAN; Ching Ming KUO (Fisheries Science, 2006)

Screening of Compactin-Resistant Microorganisms Capable of Converting Compactin to Pravastatin - Chao-Hsien Chen; Hui-Yu Hu; Yen-Ching Cho; Wen-Hwei Hsu (Current Microbiology, 2006)

Using the Selective Ion Exchange Resin Extraction and XANES Methods to Evaluate the Effect of Compost Amendments on Soil Chromium(VI) Phytotoxicity - Dar-Yuan Lee; Yu-Na Shih; Hsiu-Ching Zheng; Chiou-Pin Chen; Kai-Wei Juang; Jyh-Fu Lee; Lo Tsui (Plant and Soil, 2006)

A Natural Compound (Ginsenoside Re) Isolated from Panax ginseng as a Novel Angiogenic Agent for Tissue Regeneration - Ya-Chun Huang; Chiung-Tong Chen; Sung-Ching Chen; Po-Hong Lai; Huang-Chien Liang; Yen Chang; Lin-Chien Yu; Hsing-Wen Sung (Pharmaceutical Research, 2005)

Interaction between environmental tobacco smoke and arsenic methylation ability on the risk of bladder cancer - Yen-Ching Chen; Huey-Jen Jenny Su; Yu-Liang Leon Guo; E. Andres Houseman; David C. Christiani (Cancer Causes & Control, 2005)

Resonance Induced by Edge Waves in Hua-Lien Harbor - Guan-Yu Chen; Chung-Ching Chien; Ching-Ho Su; Hsiang-Mao Tseng (Journal of Oceanography, 2004)

Characterization and Virulence of Hemolysin III from Vibrio vulnificus - Yu-Chung Chen; Ming-Chung Chang; Yin-Ching Chuang; Chii-Ling Jeang (Current Microbiology, 2004)

Detection of cefotaxime-resistant CTX-M-3 in clinical isolates ofSerratia marcescens - Mei-Fen Tsou; Wen-Liang Yu; Siu Wan Hung; Chizh-Ju Chi; Chieh-Ju; Ssu Ching Chen; Lii-Tzu Wu (Folia Microbiologica, 2004)

Alpha-naphthoflavone induces vasorelaxation through the induction of extracellular calcium influx and NO formation in endothelium - Yu-Wen Cheng; Ching-Hao Li; Chen-Chen Lee; Jaw-Jou Kang (Naunyn-Schmiedeberg's Archives of Pharmacology, 2003)

Arsenic methylation and bladder cancer risk in Taiwan - Yen-Ching Chen; Huey-Jen Jenny Su; Yu-Liang Leon Guo; Yu-Mei Hsueh; Thomas J. Smith; Louise M. Ryan; Meei-Shyuan Lee; David C. Christiani (Cancer Causes & Control, 2003)

Noninvasive Characterization of Regional Variation in Drug Transport into Human Stratum Corneum in Vivo - Jui-Chen Tsai; Ching-Yu Lin; Hamm-Ming Sheu; Yu-Li Lo; Ying-Hsuan Huang (Pharmaceutical Research, 2003)

Calyculin A Sensitive Protein Phosphatase Is Required for Bacillus anthracis Lethal Toxin Induced Cytotoxicity - Jyh-Hwa Kau; Ching-Gong Lin; Hsin-Hsien Huang; Hui-Ling Hsu; Kuo-Ching Chen; Yu-Ping Wu; Hung-Chi Lin (Current Microbiology, 2002)

Abstracts of presentations on plant protection issues at the xth international congress of virology - E. Ramirez; A. Hernádez; E. Ham; B. L. Barrón; S. W. Ding; W. X. Li; B. J. Shi; R. H. Symons; Q. Li; K. H. Ryu; P. Palukaitis; I. B. Kaplan; et al. (Phytoparasitica, 1997)